Three birds with one stone: a disintegrable fertilizer with rapid fertilization, controlled-loss and detoxification - Xianghai Kong; Chen Sun; Ziyu You; Wanji Zhu; Xinxin Zhai; Yuhao Wang; Yan Wang; Weijian Zhang; Kaimin Zhu; Xiaoshuang Han; Pan Zhao; Yanping Zhu; et al. (Desalination, 2026)

Sample-level PRRSV RT-PCR prevalence in pigs in mainland China (2004–2025): A systematic review and meta-analysis - Mengke Si; Yiwei Wang; Xiang Li; Junxue Qiu; Xiaoyu Chong; Baolei Yang; Mingfeng Chu; Yuchen Liang; Wei Cheng; Jingyan Zhang; Xuelong Chen; Yanping Qi (Preventive Veterinary Medicine, 2026)

Benzimidazole functionalization enables efficient multi-resonance TADF with accelerated spin-flipping and balanced charge transport - Ji-Hua Tan; Si-Wei Chen; Xin-Lu Li; Han-Nan Shi; Xiao-Long Liu; Yao-Zu Su; Xiaofeng Wang; Jun-Hua Zhuang; Chengxiang Shi; Jia-Ming Jin; Shaoyun Yin; Jia-Xiong Chen; et al. (Chemical Engineering Journal, 2026)

A low-molecular-weight glucan from Lycium barbarum reprograms tumor-associated macrophages involving the Dectin-1/NOX2 axis to suppress hepatoma - Yanping Cai; Yunliang Chen; Chunjing Li; Hongxu Chen; Yi Ji; Shaojie Zhang; Ying Zhu; Shuiling Cao; Rui Xu; Xueqian Xie; Qi Yi; Qing Wang; et al. (Carbohydrate Polymers, 2026)

Upcycling lignocellulosic biomass using a radial-axial fixed-bed ex-situ catalytic pyrolysis reactor - Fuzheng Li; Jinping Guo; Xingshan Shi; Weiling Piao; Cristina Franch; Yanping Chen; K. Seshan; Songbo He (Bioresource Technology, 2026)

The Scaling Law in remote sensing mapping for model performance forecasting and reference sample optimization - Yuanhong Liao; Yuqi Bai; Shuang Chen; Jie Wang; Yanping You; Zhou Chen; Haoru Wu; Huabing Huang; Wenrui Li; Mingrun Zang; Zimeng Wang; Xinan Zhang; et al. (Remote Sensing of Environment, 2026)

Coordinate-preserving degradation-knee mapping for Kriging relevance mechanisms in FFD-based hull-form optimization - Qingwen He; Yanping He; Zhe Chen; Xin Yu; Jintao Zhou (Ocean Engineering, 2026)

Numerical investigation on the flow field characteristics and the effect of column boot clearance angle on hydrodynamic performance of deep-draft cylindrical offshore platforms - Chengming Qin; Zhe Chen; Yanping He; Yadong Liu (Ocean Engineering, 2026)

Plasma technology regulated In3S4 nanosheets surface cationic defects enhanced photocatalytic H2O2 production in pure water - Fei Li; Yang Zhang; Yongjie Zhou; Yanping Gao; Longkai Pan; Chen Sun; Hequn Yang; Fei Rao; Gangqiang Zhu (Journal of Environmental Chemical Engineering, 2026)

Magnetite-assisted hydrothermal upgrading of polyvinyl chloride into an efficient heterogeneous Fenton catalyst - Ziyi Ding; Qingze Chen; Haoyang Fu; Fangxin Deng; Yanping Zhu; Yunfei Xi; Runliang Zhu (Journal of Environmental Chemical Engineering, 2026)

Selective recovery of nickel from spent FCC catalysts using a bio-electrochemical coupled system: The synergistic role of organic acids and Eh-pH regulation - Daoqing Liu; Qianwei Li; Hao Liu; Yanping Zhu; Chunmao Chen (Journal of Environmental Chemical Engineering, 2026)

Diversity of Diaporthe species associated with post-harvest decay on kiwifruit in China - Lu Feng; Yang Lin; Chao Li; Jiatao Xie; Jiasen Cheng; Bo Li; Tao Chen; Daohong Jiang; Yanping Fu (Fungal Biology, 2026)

Long-term PFOA and cadmium Co-contamination alters soil carbon, nitrogen, and phosphorus cycling: Insights from metagenomics and metabolomics - Yanping Cai; Beihai Zhou; Shuming Liu; Chuyu Shang; Baoguo Yang; Yunqing Liu; Shengguang Zhang; Ruixue Fan; Waseem Hassan; Rongfang Yuan; Huilun Chen (Environmental Research, 2026)

Dual-responsive and CD44-targeted nanotherapy to remodel the fibrotic niche for reversing liver fibrosis - Jingwei Li; Jiahao Chen; Lingling Wang; Wei Zhao; Yan Xia; Jinhang Zhang; Jie Zhou; Haiying Song; Xinghe Ji; Zijing Zhang; Shuting Qiu; Xiandan Jing; et al. (Chemical Engineering Journal, 2026)

Unveiling microbial sulfate reduction in Acid Mine Drainage Treatment using a Chained Environmental-Microbial machine learning approach - Yanping Deng; Beiyi Xiong; Hao Chen; Yongyang Wang; Xin Liu; Chuling Guo; Zhi Dang (Chemical Engineering Journal, 2026)

An integrated experimental and computational study on a COX-2-targeted AIE probe for precise cancer cell imaging via restriction of intramolecular rotation - Jianxi Liu; Shengfa Song; Yonglin Zhang; Jiale Hu; Shulin Chen; Lulu Zhu; Li Shen; Zhen Sun; Ying Xue; Hao Jiang; Wei Ji; Jinmei Sun; et al. (Analytica Chimica Acta, 2026)

Habitat-dependent and asymmetric drivers of spectral diversity–biodiversity relationships in temperate grasslands - Yi Zhang; Yujin Zhao; Zhisheng Wu; Yanping Zhao; Wenhe Chen; Weifang Li; Zhaoju Zheng; Fei Li; Yongfei Bai (Remote Sensing of Environment, 2026)

Short-range and long-range charge transfer based narrowband deep blue organic fluorescence emitters with EQE > 20% and CIEy ≈ 0.04 - Wenyan Zhao; Zijian Chen; Jihua Tan; Zhenyue Duan; Danhong Zhou; Yanping Huo; Jiuyan Li; Ruifang Wang; Pengzhong Chen; Xiaojun Peng (Chemical Engineering Journal, 2026)

Folding integrated all-paper photoelectrochemical immunoassay using annealed ZnO for point-of-care detection of ferritin - Yibin Cai; Haining Li; Yanping Chen; Shuyi Lu; Huanhuan Zhu; Dianping Tang; Xiao Han; Shaofeng Lin (Analytica Chimica Acta, 2026)

Dysregulation of CD36 and CPT1A is associated with fatty acid metabolic disorder and cardiomyocyte injury after high-cervical spinal cord injury - Yanping Zhang; Shihong Huang; Lifei Chen; Liqin Wei; Qinfeng Huang; Linshen Huang; Hui Chen (Molecular and Cellular Biochemistry, 2026)

Synergistic effects of ultrasound-assisted freezing and NADES on the cryostability of surimi gel: Perspective of quality and molecular structure - Yue Chen; Xindi Zeng; Yanping Wang; Xinyan Li; Xin Du; Xiufang Xia (Food Chemistry, 2026)

Toward precise layer control of chemical vapor deposition growth of graphene films: from graphene to graphite - Runhan Xiao; Yangjian Xu; Chuang Tian; Jiawen Liu; Jie Cheng; Yanping Sui; Zhiying Chen; Shujie Tang; Guanghui Yu (Chemical Engineering Journal, 2026)

Numerical investigation of local convective heat transfer coefficients for a walking human model under varying wind directions - Qigui Zhou; Xiaowen Su; Yanping Yuan; Dengkai Chen; Fujian Jiang (Building and Environment, 2026)

Molecular Analysis of a New Alphapartitivirus from Rhizoctonia solani AG-4 HG III Isolate Rs292 - Yangyang Li; Yanping He; Hongyang Chu; Wenli Li; Hongyu Wang; Yi Chen; Churong Wu; Yanqiong Li (Current Microbiology, 2026)

Salvianolic Acid A Relieves Acute Lung Injury by Promoting the Expression of FOXO1 and Activating Autophagy Through the Inhibition of miR-217-5p - Xia Liu; Yanping Shi; Li Huang; Hongbo Chen; Raofei Fan; Hongzhong Zhang; Qiaofen Li; Na Yan; Maiding He; Yonghua Yang (Biochemical Genetics, 2026)

Lipopolysaccharide promotes rheumatoid arthritis by enhancing Wnt7b mediated macrophage-FLS communication - Bing Wang; Yingqiu Song; Wenbo Xu; Jiaqing Chen; Yurong Huang; Xinyue Zhou; Yikang Cai; Aixin Xia; Yanping Li; Liwei Jiang; Faxue Liao; Jian Huang; et al. (Inflammation Research, 2026)

Phage therapy: A novel strategy to combat drug-resistant Salmonella Pullorum infection in chickens - Hongzhe Zhao; Shilong You; Jiahao Fu; Xiaoyu Xiong; Yingying Ma; Xiaona Wang; Rongyan Li; Fei Teng; Mingze Chen; Wei Wu; Guiwei Li; Yanping Jiang; et al. (Veterinary Microbiology, 2026)

Defensive remodeling of gut microbiota under microplastic stress and its pathogenic mechanism - Penghua Jian; Feng Zhang; Zhihao Chen; Xuan Zhou; Yan Xiong; Qiang Hu; Yingyu Wang; Dan Li; Jiai Yan; Ju Yang; Hong Cao; Ping Wu; et al. (Chemico-Biological Interactions, 2026)

Single-nucleus RNA sequencing reveals a spatiotemporal pattern of H2S signaling in Chinese cabbage - Jiao Zhang; Yang Chen; Bo Liu; Yuwei Qin; Yue Luan; He Yin; Wenqi Liu; Limei Chen; Jixian Zhai; Yanxi Pei; Yanping Long; Zhuping Jin (Science China Life Sciences, 2026)

Assessment of Heavy Metal Pollution in Cultivated Soils and Rice Grains on the South Bank of Taihu Lake, China - Yanping Shi; Yiping Chen; Jiajia Ren; Juntao Zhao; Dan Liu (Bulletin of Environmental Contamination and Toxicology, 2026)

Integrative histological and multi-omics analyses reveal hormone-driven cell regeneration mechanisms during postharvest wound healing in melon - Congcong Wang; Yanping Hu; Baibi Zhu; Jihao Chen; Feng Wang; Shiqi Lu; Min Wang (Postharvest Biology and Technology, 2026)

Decline of beneficial microbes and proliferation of latent pathogens: Key drivers of postharvest disease in citrus - Jianghua Chen; Mengting Xu; Ting Zhu; Ziyi Yang; Juan Liu; Jie Duan; Yang Lin; Xiao Yu; Daohong Jiang; Yanping Fu (Postharvest Biology and Technology, 2026)

Carbon source determines microbial synergy and metabolic resilience in sulfate-reducing bacterial communities under nitrate stress - Yanping Deng; Siyu Zhang; Zhenchen Xie; Hao Chen; Meihui Ren; Changdong Ke; Chuling Guo; Zhi Dang (Journal of Environmental Chemical Engineering, 2026)

Chemical residues in declining commercial honey bee colonies - Zachary S. Lamas; Yanping Chen; Elina L. Niño; Dawn Boncristiani; Christopher Mayack; Arathi Seshadri; Julia Fine; Jay D. Evans (Environmental Toxicology and Pharmacology, 2026)

Narirutin Mitigates Dextran Sodium Sulfate-Induced Enteritis in Procambarus clarkii by Modulating Intestinal Microbiota - Jian Li; Yitian Chen; Yanping Cai; Huiling Zhang; Bin Qiu; Xingfei Huang; Yan Wen; Aimin Wang; Bin He; Yude Wang; Shaojun Liu (Fishes, 2026)
Enteritis is a disease that affects Procambarus clarkii, significantly impacting aquaculture due to its high incidence and mortality rates, resulting in economic losses. Currently, the molecular mechanisms behind enteritis in Procambarus clarkii are not well understood. In this study, we established a model of intestinal inflammation induced by dextran sodium sulfate (DSS). Subsequently, histopathological changes, transcriptome analysis, intestinal microbiota analysis and immunofluorescence analysis were conducted. Histopathology showed that after treatment in the DSS + Narirutin (NR) group, there was an improvement in intestinal inflammation, and the structure of the intestinal tissue was partially restored. The intestinal transcriptome analysis revealed that in the DSS + NR group, 234 genes were upregulated and 188 genes were downregulated after treatment. This indicates a significant change in gene expression. KEGG enrichment analysis revealed that the DEGs were significantly enriched in TGF-β signaling pathway and PI3K-Akt signaling pathway. The results from 16S rRNA sequencing showed that in the DSS + NR group, the relative abundance of Akkermansia muciniphila significantly increased. Immunofluorescence results showed that, compared to the control group, the expressions of Occludin, nuclear factor-kB-p65 (NfkB-p65), Zonula occludens-1 (ZO-1), and Claudin-1 decreased following DSS treatment. However, treatment with NR was able to inhibit these changes. This further validated that NR can alleviate enteritis in Procambarus clarkii.

Dynamic analysis and evaluation of gas explosion risk caused by thermal runaway of lithium-ion batteries - Yanping Zhan; Kaiyu Zou; Xiao Chen; Shouxiang Lu (Process Safety and Environmental Protection, 2026)

Study on multiscale particle motion characteristics in hydraulic lifting pipe under pulsating flow conditions - Desheng Chen; Geng Li; Wenhao Sun; Yuanming Ding; Zhe Lin; Yanping Wang (Ocean Engineering, 2026)

Influence of bow configuration on brash ice resistance: Comparison of invisible and conventional bulbous bows - Jianmei Chen; Zhe Chen; Yanping He (Ocean Engineering, 2026)

Monoglyceride-templated interfacial crystallization modulates stability and controlled release in beeswax-based double emulsions - Zengliu Song; Yanping Huang; Xinru Shi; Tianhui Feng; Xinyue Ning; Junqin Chen; Renrun Cao; Jie Xiao (Journal of Food Engineering, 2026)

Recyclable standardized sludge for performance evaluation of low-temperature drying units: Preparation and feasibility verification - Yuting Qin; Yanping Guo; Yongyou Hu; Jingyu Liu; Guanying Huang; Guanghuan Li; Haochun Chen; Qingying Huang (Journal of Environmental Management, 2026)

Comprehensive analysis of lactones and furanones in baijiu: Identification, quantitation, sensorial contribution and aging-related insights - Hao Huang; Yi Li; Huijing Lan; Jia Zheng; Dong Zhao; Jian Su; Yanping Lu; Shuang Chen; Yan Xu (Food Research International, 2026)

Zwitterionic nanoparticle-mediated interfacial hydration for robust, salt-rejecting, and anti-fouling solar steam generation - Jianbin Zhang; Yuhao Zhai; Zhichao Chen; Ting Lv; Dianming Li; Yanhua Liu; Yanping Wang; Wufang Yang; Baoli Ou; Libang Feng; Feng Zhou (Chemical Engineering Journal, 2026)

Novel Hybrid Peptide ML-2 with Antibacterial and Antibiofilm Activity Against Pseudomonas aeruginosa - Shenghua Wu; Yanping Shi; Yang He; Tao Zhang; Feilong Chen; Yingchun Zhang; Tao Wang (Current Microbiology, 2026)

Relative importance of traits, climate, and threats to extinction risk in salamanders - Jiang Wang; Chuanwu Chen; Yuyang Zhang; Yanping Wang (Conservation Biology, 2026)
Caudata (salamanders) is a highly threatened taxonomic group with over 60% of species estimated to be threatened. However, the species traits and extrinsic factors underlying their population decline and high extinction risk remain unclear. We conducted the first global comparative analysis to investigate which factors are associated with an increased risk of decline and extinction in salamanders. We addressed the following questions: Is extinction risk randomly distributed among salamander families, and if not, which families contain more threatened species than would be expected by chance; which species traits and extrinsic factors are important in determining the extinction risk in salamanders; and are the key factors for population decline consistent with those for extinction risk in salamanders? To determine which ecological characteristics and extrinsic factors best predict extinction risk and population decline in salamanders, we employed phylogenetic generalized least squares (PGLS) models and phylogenetic logistic regression (PGLM) models, respectively. Threatened salamanders were nonrandomly distributed across nine families, among which Cryptobranchidae and Hynobiidae contained significantly more threatened species than expected. Key predictors of salamander extinction risk were breeding strategy, geographic range size, minimum elevation, human threat index, and protected area coverage. Although geographic range size, climate change, and human threats were the most important predictors of salamander extinction risk and population decline, the effect of geographic range size was the opposite between the PGLS and PGLM models. Our results suggest that priority management should focus on extinction‐prone families, particularly Cryptobranchidae and Hynobiidae, and salamanders with small range sizes and sensitivity to human disturbance or climate instability.

Surface reflectance in homogeneous regions follows a Gamma distribution: principles, validation and applications - Yuanhong Liao; Yuqi Bai; Yanping You; Jie Wang; Shuang Chen; Ming Lin; Jin Chen; Jing M. Chen; Bing Xu; Peng Gong (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Evaluating microphysics scheme impacts on summer precipitation in Northwestern China using a convection permitting WRF model - Ya Huang; Qingyun Duan; Yong Zhao; Lihua Chen; Yanping Li (Atmospheric Research, 2026)

Railway CORS GNSS PWV forecasting using normal time-frequency transform and deep learning with transfer learning strategy - Chen Chang; Yanping Liu; Yong Wang; Yunlong Zhang; Xiangshun Meng; Haozhe Chi; Chunrui He (Advances in Space Research, 2026)

The atmospheric residual error model of time-series InSAR based on ERA-5 PWV in Beijing, China - Haozhe Chi; Yong Wang; Yunlong Zhang; Chengwu Yang; Chen Chang; Fei Qiao; Xiangshun Meng; Chunhong Liu; Yanping Liu (Advances in Space Research, 2026)

Numerical Study on the Effect of Column Boot Diameter-to-Height Ratio on the Hydrodynamic Performance of Deep-Draft Cylindrical Offshore Platforms - Chengming Qin; Zhe Chen; Yanping He; Yadong Liu (Journal of Marine Science and Engineering, 2026)
For deep-draft cylindrical platforms with a large annular column boot, the influence of the column boot diameter-to-height ratio (d/h) on motion performance remains unclear. This study investigates the effect of d/h on platform hydrodynamics while keeping the main body geometry, displacement, and draft unchanged. A hybrid numerical model validated against tests is adopted: STAR-CCM+ free-decay simulations identify equivalent linear damping, and ANSYS AQWA predicts hydrodynamic coefficients, response amplitude operators, and coupled time-domain responses under a 100-year survival sea state in the western South China Sea. Increasing d/h substantially increases heave added mass and added pitch moment of inertia, leading to longer natural periods and higher damping in heave and pitch. However, its effect on motion responses is non-monotonic and strongly response-dependent. As d/h increases, the responses are initially reduced markedly. The minimum surge and heave responses occur at d/h = 2.39 and 4.67, with reductions of about 34.0% and 87.2%, respectively, while the pitch response is already reduced by about 67.3% at d/h = 7.22. Further increases in d/h may weaken surge and heave mitigation while providing limited additional benefit for pitch. These findings provide qualitative understanding and quantitative guidance for response-oriented column boot design and optimization of similar platforms.

A three-dimensional layered model for sea area usage across dimensions of space, functional elements, and time - Saiya Xu; Yanping Li; Qi Yue; Dahai Liu; Heng Hu; Shuo Wang; Yuqing Chen; Yilin Liu (Ocean & Coastal Management, 2026)

Local macrophage dynamics–inspired engineering of time-programmed nano-vaccine scaffold for postoperative cancer immunotherapy - Zhenyu Xu; Qian Chen; Mingyu Hao; Yiyang Cao; Xiaoqin Kuang; Chunjiayu Li; Zhihao Liu; Jiawen Xue; Jianing Zhao; Mengwei Zhao; Naicong Cai; Yiqing Li; et al. (Science Bulletin, 2026)

Pa-miR396 targets PaGRFs to disrupt PaGRF–PaGIF transcriptional activation in Platanus acerifolia leaf development - Yongkang Lu; Yuqing Chen; Dasui Li; Manzhu Bao; Yanping Zhang (Plant Science, 2026)

Expansion of the rhizosphere soil and phyllosphere bacterial resistomes following repeated farmland application of high-temperature granulation-treated antibiotic fermentation residues - Ruiqi Wan; Tianyu Chen; Yanping Xun; Yazhuo Chen; Jitao Lv; Lingyi Meng; Kristian Koefoed Brandt; Yawei Wang (Journal of Environmental Sciences, 2026)

Divergent responses of maize and soybean to intercropping: Insights from arbuscular mycorrhizal fungi diversity, colonization, and related-genes expression - Shihui Yu; Xinru Liu; Ling Liu; Yanping Ma; Baohong Liu; Wuyan Xiang; Ying Zhang; Peiyong Liu; Chen Feng; Caixia Sun (Plant and Soil, 2026)

Balancing Accuracy and Speed: Improved D-FINE for Real-Time Ocean Internal Wave Detection - Lu Yu; Yanping Tian; Jie Chen; Cheng Chi; Tingting Li; Jianwei Li (Journal of Marine Science and Engineering, 2026)
Ocean internal waves (IWs), induced by density stratification and fluid perturbations, are significant oceanic phenomena prevalent across global oceans, profoundly impacting marine environments and engineering safety. Although one-stage object detection models are favored in practical applications due to their efficient inference, they often suffer from insufficient accuracy in IW detection tasks. To address this, we introduce a novel one-stage, anchor-free detection approach based on Transformer for IW detection, proposing a new algorithm named IW-D-FINE, which balances detection accuracy and inference efficiency. On the public SAR dataset, IW-D-FINE achieves an AP@0.5 of 90.5, significantly outperforming existing one-stage methods while maintaining faster inference speeds than mainstream two-stage models. Furthermore, to mitigate the scarcity of internal wave samples, we construct a small-scale IWs dataset, YH3-IW-2025, and validate the algorithm thoroughly on this dataset. Experimental results demonstrate that IW-D-FINE exhibits robust performance under complex background interference, highlighting its application potential and scalability in IW detection tasks.

Deciphering the spatiotemporal dynamics and source characteristics of nutrients under anthropogenic pressure in Taipu River, China - Tong Wang; Jiayi Kou; Fengjunxi Chen; Yalong Li; Yaojen Tu; Yanping Duan (Journal of Contaminant Hydrology, 2026)

Long-distance lateral migration, accumulation and dissipation of natural gas in the northeastern Ordos Basin, China - Yang Qin; Chiyang Liu; Junfeng Zhao; Faqi He; Wei Zhang; Yanping Ma; Lihua Yang; Deyong Shao; Nan Du; Fuyu Chen (Gondwana Research, 2026)

Multi-omics analyses unveil the molecular mechanism involving flavonoid-mediated color changes of different mango varieties - Yibo Bai; Min Zhu; Bang Du; Yanping Zheng; Aiping Gao; Jianfeng Huang; Yeyuan Chen; Rulin Zhan; Huarui Chen; Xintao Lei; Zhiguo Dang (Food Chemistry, 2026)

Pou4f3 Deficiency Obstructs the Subtype Differentiation of Vestibular Hair Cells - Qin Zhou; Yikang Huang; Wenli Ni; Mingchuan Feng; Lingjie Wu; Chuijin Lai; Yanping Zhang; Wenyan Li; Yan Chen (Neuroscience Bulletin, 2026)

Synthesis and biological evaluation of coumarin-based urea derivatives demonstrating apoptosis-inducing and anti-angiogenic properties for non-small cell lung cancer treatment - Zirui Chen; Qi Liao; Pengyu Zhao; Yuefei Geng; Jianguo Wen; Shu Liu; Yanping Tang; Chenjuan Zeng; Tingting Yan; Yongmei Shen; Funeng Geng (Medicinal Chemistry Research, 2026)

Experimental study on boiling heat transfer of water flowing in a mini zigzag tube - Yihang Wu; Tianzhou Xie; Shenghui Liu; Jianjun Xu; Shuangqing Chen; Xiaoliang Zhu; Yanping Huang; Muhammad Jahanzaib; Junlin Huang; Ruiying Gao (Annals of Nuclear Energy, 2026)

Analysis of atmospheric residual error and construction of correction model for GACOS-Corrected PS+DS time-series InSAR based on ERA5 PWV - Fei Qiao; Yong Wang; Yunlong Zhang; Chen Chang; Haozhe Chi; Chunhong Liu; Xiangshun Meng; Yanping Liu; Chengwu Yang (International Journal of Remote Sensing, 2026)

The Evolution and Development of Integrated Coastal Zone Management in China Since the 1950s - Yanping Li; Wenjing Zheng; Tuanxi Dong; Yingzi Yang; Shuo Wang; Yinuo Kang; Yilin Liu; Yuqing Chen; Dahai Liu (Coastal Management, 2026)

Ethylene production from chlorinated organic hazardous wastes by thermal plasma pyrolysis - Yanping Yu; Hao Li; Wenlong Dong; Jiachen Zhu; Jiaqi Xu; Chen Wang; Baogen Su; Wenjun Zhang; Zhongbiao Wu; Qilong Ren; Qiwei Yang (Journal of Hazardous Materials, 2026)

Sustainable upcycling of solid waste into heterogeneous peroxymonosulfate activators for degrading emerging organic contaminants in wastewater - Shuhua Wang; Yanping Zhong; Yiping Chen; Zhenguo Chen (Journal of Environmental Management, 2026)

Exfoliation characteristics of tetrahydrofuran on surface-active structure of different coals and its inhibition effect on oxidation - Jun Guo; Yunfei Wu; Hu Wen; Yin Liu; Yongfei Jin; Changming Chen; Yanping Quan (Fuel, 2026)

Targeting Phospholipid Metabolism as an Effective Hearing Protection Strategy - Huanyu Mao; Wenli Ni; Lupeng Ma; Xiang Li; Yanping Zhang; Yuzheng Zhao; Wenyan Li; Huawei Li; Yan Chen (Neuroscience Bulletin, 2026)

The effect of CD40 agonist antibody therapy on the pancreatic cancer microenvironment - Yilan Ma; Jin Ding; Yanping Chen (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

A new method of consistency evaluation of brain drugs: a case study of edaravone - Liqiang Gu; Yanping Hu; Yinfang Lai; Sheng Zhang; Haoran Wang; Xiaozhen Xu; Lingfang Chen; Yuhua Shi; Jiechao Chen; Xiaochun Sun; Yuan Zhang; Lingzhi Hu (Regulatory Toxicology and Pharmacology, 2025)

Research on hourly precipitation prediction along railways based on ERA5 reanalysis and post-processing correction - Xiangshun Meng; Yong Wang; Yunlong Zhang; Chengwu Yang; Chen Chang; Haozhe Chi; Yanping Liu (Journal of Atmospheric and Solar-Terrestrial Physics, 2025)

Study on the mechanism of influence of group extraction on low-temperature spontaneous combustion characteristics of lignite - Changming Chen; Jun Guo; Hu Wen; Yin Liu; Bo Gao; Yunfei Wu; Yanping Quan (Fuel, 2025)

Revealing the polyphenol modulation mechanism for in vitro gastric digestion properties of myofibrillar proteins via noncovalent interaction - Yan Lu; Chaoqun Chen; Yu Chen; Shuaiqian Wang; Yanping Hu; Ping Liu; Hongbin Lin; Jie Tang; Jie Zhao (Food Chemistry, 2025)

Multifunctional groups improved photoluminescence efficiency of hot exciton materials for blue OLEDs with a maximum external quantum efficiency exceeding 12 % - Xiaofen Zhuang; Yuwei Xu; Ruicheng Wang; Tingting Cao; Jinxiang Li; Zhiju Chen; Yueling Ma; Dehua Hu; Yaocheng Jin; Wen-cheng Chen; Xianwei Li; Shaomin Ji; et al. (Chemical Engineering Journal, 2025)

Biochar-Amended Composting Transforms Chicken Manure Waste Into a Resource: Enhancing Extra-Rhizosphere Soil Fertility and Shaping Microbial Communities - Longjun Chen; Haiping Fan; Lulong Zhong; Yuncai Wang; Cheng Chen; Xin Chen; Yanping Chen; Jiaolin Zhang; Yu Lin (Journal of Soil Science and Plant Nutrition, 2025)
This study elucidates the synergistic regulatory mechanisms of biochar-amended chicken manure and mushroom residue compost (BCM) on soil microbial communities and nutrient cycling in the extra-rhizosphere, while evaluating its potential for sustainable agricultural waste recycling. Methods: We conducted a 50-day composting trial using five biochar application rates (0–7%). Assessed parameters included compost maturity (C/N ratio), nutrient content (NO 3 − -N, available phosphorus [AP], soil organic matter [SOM]), phosphatase and catalase activities, microbial community composition, and metabolic pathways. We performed Redundancy analysis (RDA) to correlate SOM/AP dynamics with microbial diversity and functional pathways. Results: At 5–7% biochar, compost maturity improved significantly, with C/N ratios of 15.6–18.2 and 2.2-4.0-fold increases in NO 3 − -N (1.41 mg/g), AP (50.09 mg/kg), and SOM (166.11 g/kg). Enzymatic activities (phosphatase: 9.81 mg/g·24 h; catalase: 83.08 µmol/g·24 h) correlated strongly with SOM/AP (R 2 = 0.71–0.82). Biochar enriched Proteobacteria (34.1%) and Actinobacteriota (15.2%), suppressed Halophiles ( Halomonas reduced by 52%), and enhanced carbon metabolism and oxidative phosphorylation pathways. RDA identified SOM/AP as a key driver of microbial diversity (R 2 = 0.91). The 5% biochar dose optimized nutrient retention (37–59% increases in AP, Available potassium [AK], NO 3 − -N) while maintaining microbial diversity, outperforming higher doses. Conclusions: This study demonstrates biochar’s dual role in reshaping extra-rhizosphere microbial ecology and nutrient dynamics, offering a precision agriculture strategy for sustainable waste recycling and circular economy practices. The 5% biochar dosage proved optimal, enhancing nutrient cycling and microbial activity while mitigating halophilic microbial suppression. Graphical Abstract

Erratum to: Rapid Post-Earthquake Impact and Recovery Assessment: The 2025 Mw 7.7 Myanmar Earthquake - Wenkai Chen; Jiajie Wu; Gang Rao; Xue Li; Lize Chen; Yuyang Peng; Zhenhang Zhang; Ming Yi; Yanping Sun (Journal of Earth Science, 2025)

Complete genome sequence and molecular characterization of a novel potyvirus (sweet potato virus H) infecting sweet potato - Wei Tang; Jukui Ma; Yanping Tian; Xiao Yin; Jingwei Chen; Dongjing Yang; Fangyuan Gao; Zhao Liang; Cong Tong; Chengling Zhang; Houjun Sun (Archives of Virology, 2025)

Demand for small‐ and large‐ranged reptiles in worldwide wildlife trade - Songqi Zhang; Shai Meiri; Marcel Holyoak; Jiang Wang; Yanping Wang; Chuanwu Chen (Conservation Biology, 2025)
Wildlife trade poses a major threat to biodiversity, yet the drivers determining which species are traded are not fully understood. Through a comprehensive collection of official and online trade data, we applied a binomial test to identify families that contain an unexpectedly large or small number of traded species. We also analyzed which factors predispose reptile species to be traded and explored whether traded species were more likely to be threatened with extinction. Of the 10,919 reptile species in our dataset, 3889 species (35.6%) were traded. There was strong evidence for taxonomic biases in trade risk. In particular, all turtle and crocodilian families had higher trade risk than other reptiles. Species with large body sizes, habitat generalists, insular endemics, and those found in regions with high gross domestic product were traded in greater quantities and more frequently. Species with small and large ranges were more frequently involved in trade, suggesting a demand for rare and common species in wildlife trade. When connecting trade risk to extinction risk, data‐deficient and not‐evaluated species had fewer traded species and were less likely to be traded than threatened or nonthreatened ones. Nonetheless, these species warrant special conservation attention considering their rarity, limited range size, and insufficient legal protection. Given the increased attention given to wildlife trade, we suggest implementing stronger regulatory measures to monitor and control the trade of reptile species, particularly those belonging to families with a high risk of being traded. Efforts should also prioritize the protection of species exhibiting traits that make them highly susceptible to exploitation. Finally, promoting international collaboration for stricter enforcement of wildlife trade regulations and support of sustainable trade practices can help mitigate the negative impacts on biodiversity.

New interpretation of the Rb/Sr ratio of the Ili loess, northeastern Central Asia - Yanping Wang; Yougui Song; Yue Li; Hamid Gholami; Haoru Wei; Mengxiu Zeng; Xiuling Chen; Li Han (Quaternary Science Reviews, 2025)

Valorizing industrial and agricultural wastes into a high-performance composite for remediation of heavy metal-contaminated tailing sands - Mengjia Liang; Man Xue; Yanping Shi; Jihua Cai; Xianyu Yang; Chunzheng Jin; Zexin Chen; Maoyan Xu (Environmental Research, 2025)

Formation of N-doped carbon nanosheets encapsulated hollow Co1/3Fe2/3P nanocrystals via the nanoscale Kirkendall effect as anode for superior alkali-ion batteries - Xijun Xu; Suping Chen; Fangkun Li; Panpan Zhang; Yanping Huo; Jun Liu (Chemical Engineering Journal, 2025)

Reaction route innovates design of metal supported single atom electrocatalysts for hydrogen evolution: A review - Zeyu Zhao; Ting Chen; Bing Ding; Shengliang Zhang; Duo Chen; Gao Chen; Yanping Zhu; Xiaogang Zhang (Chemical Engineering Journal, 2025)

Editorial Expression of Concern: The nuclear translocation of endostatin is mediated by its receptor nucleolin in endothelial cells - Nan Song; Yanping Ding; Wei Zhuo; Ting He; Zhiguang Fu; Yang Chen; Xiaomin Song; Yan Fu; Yongzhang Luo (Angiogenesis, 2025)

Insights into stress response pathways and potential triterpene accumulation mechanisms induced by friction damage in kiwifruit - Fan Yang; Yuchun Wang; Fangzhi Wu; Sike Wang; Yuduan Ding; Yue Chen; Qinggang Zhu; Yanping Ma (Postharvest Biology and Technology, 2025)

Efficient activating peracetic acid by copper-aluminum composites to degrade sulfathiazole: The critical role of Cu(III) species - Yuxiao Mu; Yanping Ding; Linli Tan; Qiulin Shi; Lei Chen; Jiaqi Ding; Jingwen Wang; Yong Liu; Pengchao Xie (Journal of Environmental Chemical Engineering, 2025)

Phase change nanoemulsions developed by a modified phase inversion temperature method for low-temperature thermal energy storage - Songping Mo; Wenke Cheng; Junhao Chen; Yuxuan Lin; Zicai Pan; Zhi Yang; Lisi Jia; Yanping Du; Ying Chen (International Journal of Refrigeration, 2025)

Homogeneous bioluminescent immunosensor for aflatoxin B1 detection via unnatural amino acid-based site-specific labeling - Mengna Chen; Yanping Li; Qinghua He; Junjie Zeng; Xiaojiang Li; Zhui Tu (Food Control, 2025)

High entropy relaxation ferroelectric ceramics with strong coupled achieved by framework structure guided design and grain boundary optimisation - Renkai Zhao; Kaijie Chen; Wenhua Li; Xingui Tang; Zhifei Jian; YongXi Liang; Jiayi Yin; Yanping Jiang; Xiaobin Guo; Kai Yan (Chemical Engineering Journal, 2025)

Evolution and prediction of drought-flood abrupt alternation in mainland China using an improved index - Yiming Tong; Yu Chen; Yanping Qu; Virgílio A. Bento; Hongquan Song; Han Qiu; Wei Shui; Jingyu Zeng; Qianfeng Wang (Climate Dynamics, 2025)

Rapid Post-Earthquake Impact and Recovery Assessment: The 2025 Mw 7.7 Myanmar Earthquake - Wenkai Chen; Jiajie Wu; Gang Rao; Xue Li; Lize Chen; Yuyang Peng; Zhenhang Zhang; Ming Yi; Yanping Sun (Journal of Earth Science, 2025)

Resveratrol inhibits autophagy in cardiomyocytes subjected anoxia/reoxygenation injury: involved in VDAC1/PINK1/Parkin pathway - Ying Zhou; Yongzhe Huang; Haiyan Liang; Xiaomei Yang; Shulin Zhang; Yinru Huang; Yanping Wan; Hangfei Zhou; An Huang; Yue Chen; Xiao Li; Yian Peng; et al. (Toxicology and Applied Pharmacology, 2025)

Enhanced Sb(V) removal from sulfate-rich wastewater by anaerobic granular sludge: Role of AQS-loaded iron sludge-derived hydrochar - Qi Li; Yanping Zhu; Xiong Zheng; Yinguang Chen; Hongying Yuan; Nan Jiang; Mengying Yan; Manhong Huang (Journal of Water Process Engineering, 2025)

Nosema or Vairimorpha: Genomic/proteomic support to a complex socio-economic issue rooted in taxonomic change - Jamie Bojko; James Becnel; Edouard Bessette; Sam Edwards; Jing Gao; Wei-Fone Huang; Nataša Katanić; Amjad Khalaf; Tian Li; Jonathan W. Snow; Leellen F. Solter; Cheyenne E. Stratton; et al. (Journal of Invertebrate Pathology, 2025)

Expert consensus on cryosurgery therapy of mucosal melanoma on head and neck - Yadong Wu; Guoxin Ren; Moyi Sun; Zhangui Tang; Longjiang Li; Jian Meng; Zhijun Sun; Shaoyan Liu; Yue He; Wei Shang; Bo Li; Jie Zhang; et al. (Cryobiology, 2025)

Stem nematode disease resistance-conferring gene identification in sweet potato using combined BSA-Seq and BSR-Seq analyses - Shouchen Qiao; Jingwei Chen; Yawei Li; Yannan Wang; Jukui Ma; Zhihe Kang; Qianqian Bian; Guozheng Cao; Guorui Zhao; Guohong Yang; Yanping Fan; Houjun Sun; et al. (Planta, 2025)

Development of tissue culture techniques and comparative metabolomics for Echeveria ‘Pretty in Pink’ calli - Shuangbin Fu; Zhen Ying; Chaoxiang Chen; Yanping Yang (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)

The behavior of NOM-Cu(Ⅱ)colloids at the goethite interface - Yuekang Chen; Lijuan Zeng; Kai Chen; Meiling Yin; Xiongkai Zheng; Yuting Zhou; Yanping Deng; Jiehong Ye; Zhi Dang; Chuling Guo (Water Research, 2025)

Enhanced extraction of microplastics from terrestrial animal intestinal tissues via optimized fenton oxidation - Simin Yu; Jiaqi Chen; Zhanao Zhang; Yanping Zhao; Yan Zhang (Journal of Hazardous Materials, 2025)

Trapping phenylacetaldehyde by litchi shell polyphenols and their characteristic catechins in chemical model and roast pork patty: Identification of catechins-adducts and toxicity assessment - Qi Chen; Yanping Xian; Ming Liang; Min Qian; Qingping Wu; Qi He; Xiaofang Zeng; Weidong Bai; Hao Dong (Food Chemistry, 2025)

OCCMNet: Occlusion-Aware Class Characteristic Mining Network for multi-class artifacts detection in endoscopy - Chenchu Xu; Yu Chen; Jie Liu; Boyan Wang; Yanping Zhang; Jie Chen; Shu Zhao (Medical & Biological Engineering & Computing, 2025)

The impact of season, temperature, and direct normal irradiance on IVF pregnancy outcomes: a retrospective cohort study - Chao Wang; Jiehua Chen; Zhong Lin; Li Shi; Qiuyan Ruan; Jiamin Long; Yanping Lao; Xiangli Niu (International Journal of Biometeorology, 2025)
Objective . This study assessed associations between season, temperature, direct normal irradiance (DNI), and clinical pregnancy outcomes in first fresh in vitro fertilization (IVF) cycle. Methods . We conducted a retrospective cohort study (June 2021-October 2023) of 1179 patients undergoing fresh IVF cycles. Inclusion criteria required age ≤ 45 years, first-time fresh embryo transfer cycles (long/antagonist protocol), excluding preimplantation genetic testing, frozen cycles, or incomplete data. Temperature and DNI were recorded from gonadotropin (Gn) initiation to oocyte retrieval. Binary logistic regression assessed seasonal impacts on clinical pregnancy, while restricted cubic splines (RCS) independently modeled temperature/DNI effects. Results . Compared to winter, clinical pregnancy likelihood was 1.74-fold higher in spring (95% CI:1.11–2.71, P = 0.015) and 1.53-fold in summer (95% CI:1.02–2.30, P = 0.042). Stratified analysis revealed a 2.02-fold increased likelihood in summer cycles using the long protocol (95% CI:1.07–3.82, P = 0.031), whereas no seasonal variation was observed in antagonist protocol. RCS regression analysis indicated a nonlinear relationship between temperature and clinical pregnancy outcomes, which was confirmed in the long protocol group. No significant correlations were observed with DNI or in patients treated with the antagonist protocol. Conclusions . Season and ambient temperature significantly impact IVF clinical pregnancy, especially in the long protocol, with the highest increase in pregnancy rates observed in summer, as well as within the 26.13℃ to 29.68℃ temperature range. No significant effects were observed with DNI or the antagonist protocol. These findings suggest that summer treatment may optimize IVF outcomes, but future studies should prioritize multi-center prospective designs with continuous temperature monitoring to define precise optimal ranges.

Dynamics of wall bubbles in flash evaporation systems: Heterogeneous expansion and microlayer development - Qifan Wang; Junren Hou; Shanfang Huang; Fangbei Chen; Minyun Liu; Ruohan Zheng; Yanping Huang; Lie Quan; Houjun Gong; Yu Tang (Annals of Nuclear Energy, 2025)

Dust supply to the West Philippine Sea since the Middle Pleistocene and distinct influences of the Westerlies after the Mid-Brunhes Event - Yun Cai; Dong Xu; Haifeng Wang; Yanping Chen; Haiyan Jin; Yibing Li; Weiwei Chen; Liang Yi (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Polyphenylene molecular engineering enables highly efficient multi-resonance thermally activated delayed fluorescence emitters with quenching resistance - Longjiang Xing; Xiaofeng Wang; Xiaolong Liu; Wen-Cheng Chen; Shihao Liu; Siwei Chen; Mengke Li; Ji-Hua Tan; Jia-Ming Jin; Ruicheng Wang; Shangru Li; Shaomin Ji; et al. (Chemical Engineering Journal, 2025)

Synthesizing ZIF-8 functionalized biochar by in situ reuse of residual Zn from chemical activation for enhanced tetracycline hydrochloride adsorption removal - Jianying Liu; Qian Zeng; Yao Chen; Zhongde Dai; Wenju Jiang; Lu Yao; Junfeng Zheng; Dengrong Sun; Yanping Wu; Lin Yang (Journal of Environmental Chemical Engineering, 2025)

Effects of Fe3O4 on production of even-carbon volatile fatty acids by anaerobic fermentation of kitchen waste under ultrasonic-alkali pretreatment: Performance, metabolic functions, and metabolic pathways - Ziang Wang; Rufei Liu; Yue Cui; Zhihan Zhang; Huiyan Jing; Zhiling Chen; Shen Tian; Ziyi Yang; Yanping Liu (Journal of Environmental Chemical Engineering, 2025)

A gut bacterial supplement for Asian honey bee (Apis cerana) enhances host tolerance to nitenpyram: Insight from microbiota–gut–brain axis - Chonghui Zhao; Yehua Peng; Muhammad Fahad Raza; Wenbo Wang; Yi Zhang; Yanping Chen; Richou Han; Jun Guo; Shaokang Huang; Wenfeng Li (Environmental Research, 2025)

Synergizing lattice matching and transient N–Li bonds to boost sulfur redox kinetics and regulate uniform lithium deposition in practical Li–S batteries - Yantao Wang; Huiqin Chen; Wenjuan Wu; Jinlong Li; Guangxin Zhang; Chunyan Wei; Shiyu Wang; Linlin Zhang; Yanping Zheng; Huanhuan Li (Chemical Engineering Journal, 2025)

Overcrowded steric engineering of through-space interactions for anti-quenching multi-resonance TADF materials - Ru-Jia Wang; Fan Zheng; Jie Hu; Yu-Lan Wu; Xiao-Long Liu; Jia-Xiong Chen; Longjiang Xing; Qiao-Er Wu; Yanping Huo; Wen-Cheng Chen (Chemical Engineering Journal, 2025)

Alkaline-thermal synergistic activation of persulfate for sawdust hour-level humification to prepare fulvic-like-acid fertilizer - Dongfang Wang; Xinyan Chen; Jing Zhang; Jia Xu; Xianghai Kong; Jinghong Ye; Rongjun Zhang; Huiqun Fan; Li Liu; Xiuping Zhan; Yan Qin; He Xu; et al. (Bioresource Technology, 2025)

Topping-induced transcriptome changes reveal PaSPL-mediated regulation of plant architecture in Platanus acerifolia - Yanping Zhang; Yali Guan; Yongkang Lu; Lin Wang; Yuqing Chen; Manzhu Bao (Plant Molecular Biology, 2025)

Recognition and classification techniques of marine mammal calls based on LSTM and expanded causal convolution - Wanlu Cheng; Hao Chen; Jiaming Jiang; Shuang Li; Jingjing Wang; Yanping Zhou (Frontiers in Marine Science, 2025)
Marine mammal calls play a vital role in navigation, localization, and communication. Effectively classifying these calls is essential for ecological monitoring, species conservation, and military biomimetic applications. However, traditional machine learning methods struggle to capture complex acoustic patterns, while most existing deep learning approaches rely solely on frequency-domain features and require large datasets, which limits their performance on small-scale marine mammal datasets. To address these challenges, we propose a hybrid architecture combining a time-attention Long Short-Term Memory (LSTM) network and a multi-scale dilated causal convolutional network. The model comprises three modules: (1) a frequency-domain feature extraction module employing dilated causal convolutions at multiple scales to capture multi-resolution spectral information from Mel spectrograms; (2) a time-domain feature extraction module that inputs Mel-frequency cepstral coefficients (MFCCs) into an LSTM enhanced with a time-attention mechanism to highlight key temporal features; and (3) a classification module leveraging transfer learning, where a pre-trained neural network is fine-tuned on real marine mammal call data to improve performance. Extensive experiments were conducted on vocalizations from four marine mammal species. Our proposed method outperformed existing baseline models across four evaluation metrics: accuracy, precision, recall, and F1 score, with improvements of 3%, 7%, 2%, and 4%, respectively. The results confirm the effectiveness of combining frequency- and time-domain features along with attention mechanisms and transfer learning. This hybrid approach enhances the accuracy and robustness of marine mammal call classification, especially under limited data conditions.

Advancements in lipid-based delivery systems for functional foods: a comprehensive review of literature and patent trends - Xidong Liu; Zengliu Song; Wenni Tian; Abdullah; Qingrong Huang; Meimiao Chen; Yanping Huang; Hang Xiao; Jie Xiao (Critical Reviews in Food Science and Nutrition, 2025)

Preparation of a polysulfone loose nanofiltration membrane with gradient structure via hybrid-induced phase separation for the efficient separation of dyes/salts - Yuanhui Tang; Huifang Yu; Yuwenyao Zhang; Juan Liu; Jihao Zhu; Yakai Lin; Hedi Chen; Yanping Hu; Jianqing Zhang; Song Hu; Hai Xie; Lixin Yu; et al. (Desalination, 2025)

Postharvest fragrance dynamics of different scented cut lilies: Insights from HS–SPME–GC–MS and electronic nose - Yiwei Zhou; Yiwei Chen; Jinfeng Dong; Qin Wang; Fulong Yan; Jianjun Tan; Yechun Xu; Genfa Zhu; Yanping Fan; Yuanjun Ye (Postharvest Biology and Technology, 2025)

Identification of candidate genes associated with resistance to aflatoxin production in peanut through genetic mapping and transcriptome analysis - Dongxin Huai; Li Huang; Xiaomeng Xue; Bolun Yu; Yingbin Ding; Gaorui Jin; Hao Liu; Manish K. Pandey; Hari Kishan Sudini; Huaiyong Luo; Xiaojing Zhou; Nian Liu; et al. (Theoretical and Applied Genetics, 2025)

Thermal deformation analysis of the Advanced Space-Based Solar Observatory (ASO-S) in orbit based on payloads measurement - Zhongguang Yang; Lei Deng; Cheng Zhu; Zengshan Yin; Tao He; Yu Huang; Yanping Bai; Hu Jiang; Yong Yang; Ye Zhang; Binglong Chen; Xinyu Li; et al. (Advances in Space Research, 2025)

WD40 proteins PaTTG1 interact with both bHLH and MYB to regulate trichome formation and anthocyanin biosynthesis in Platanus acerifolia - Qi Mengxuan; Tian Xinyue; Chen Yuqing; Lu Yongkang; Zhang Yanping (Plant Science, 2025)

Automated calibration of Noah-MP land surface model for improved irrigation representation in the North China Plain - Danqiong Dai; Yanping Li; Liang Chen; Fei Chen; Zhenhua Li; Zhe Zhang; Prasanth Valayamkunnath; Li Xu; Cenlin He; Zhuguo Ma (Journal of Hydrology, 2025)

Research on the impact of the belt and road initiative on the carbon emission performance of countries along the route - Jing Li; Yanping Zhou; Huiying Chen (Environment, Development and Sustainability, 2025)

Suyin Detoxification Prescription Regulates the Klotho and ERK/NF-κB Signaling Pathways to Alleviate Renal Injury - Lianghui Shu; Li Quan; Yanping Wang; Yanlin Chen; Chen Yong; Fang Tian; Kun Gao; Enchao Zhou (Cell Biochemistry and Biophysics, 2025)

The importance of organic matter in controlling the metal variability and mobility in seagrass sediments - Shanshan Chen; Shiquan Chen; Zhenghua Tao; Yanping Li; Paolo Magni; Li Zhang; Xinqing Zheng; Ke Pan (Environmental Pollution, 2025)

Birnessite enhanced Cr(III) oxidation during subsurface geochemical processes: Role of Mn(III)-induced nonphotochemical reactive oxygen species - Yuting Zhou; Chuling Guo; Yanping Deng; Yanjun Jiang; Meiling Yin; Kai Chen; Siyu Zhang; Guining Lu; Zhi Dang (Environmental Pollution, 2025)

New insights into interfacial dynamics and mechanisms of biochar–derived dissolved organic matter on arsenic redistribution in Schwertmannite - Xiaofei Li; Tianfu Li; Yanfu Wei; Xiaohu Jin; Suresh C. Pillai; Jun Zhang; Dian Chen; Xiaolian Wu; Yanping Bao; Xueding Jiang; Hailong Wang (Environmental Pollution, 2025)

Fluorinated Zn-porphyrin covalent organic frameworks with optimized hydrophobic/hydrophilic balance towards stable Zn anodes - Xia Li; Yanping Chu; Shouliang Lu; Liangdan Chen; Long Su; Fei Lu; Zhen Chen; Xinpei Gao (Chemical Engineering Journal, 2025)

Identification and characterization of Morganella morganii strain YC12-C3 and Enterococcus faecalis strain YC12-C10 and elucidation of its deoxynivalenol-degrading potential - Jiuchun An; Yefei Chen; Shihua Zhou; Yanping Gao; Changgui Yang; Jinqiang Zhang; Xiaohong Ou; Yanhong Wang; Weike Jiang; Tao Zhou; Qing-Song Yuan (Mycotoxin Research, 2025)

Development of system analysis code and its application in transient simulation of supercritical CO2 Brayton cycle direct cooled reactors - Haijie Wu; Minyun Liu; Shenghui Liu; Jiatao Meng; Shuangqing Chen; Ruohan Zheng; Yanping Huang; Houjun Gong; Xiaoliang Zhu; TianYang Xing; Mudi Jiang (Annals of Nuclear Energy, 2025)

Temporal dynamics of summer phytoplankton communities and their response to environmental changes in the northern Yellow Sea (2011-2020) - Yibo Wang; Zhiliang Liu; Yanping Qi; Yang Chen; Haibo Zhang; Xihan Liu; Du Su (Frontiers in Marine Science, 2025)
Research on phytoplankton distribution and dynamics is crucial for understanding marine ecosystem functions and evaluating their status. The northern Yellow Sea (NYS), a marginal sea of the Pacific Ocean, has experienced significant anthropogenic impacts since the late 20 th century, resulting in an increased nitrogen-to-phosphorus (N/P) ratio and heightened phosphorus limitation. These changes are considered critical factors affecting the phytoplankton community structure in the NYS over recent decades. This study analyzed the temporal dynamics of environmental factors and phytoplankton community structure in the NYS during the summers from 2011 to 2020, aiming to elucidate recent changes in phytoplankton community structure and their driving forces. The results indicated a significant decrease in dissolved inorganic nitrogen (DIN) concentration after 2011, resulting in a decreased N/P ratio, while phosphorus limitation persisted. Temperature, temperature gradient (reflecting stratification intensity) and salinity exhibited upward trends, whereas pH, nitrogen-to-silicon (N/Si) ratio, and chlorophyll- a concentration showed downward trends. The abundances of total phytoplankton, Bacillariophyta, and Dinoflagellata, as well as the Dia/Dino index, fluctuated annually and correlated with temperature, temperature gradient, and nutrient structure. Diversity indices remained stable throughout the study period. The Yellow Sea Cold Water Mass prominently influenced summer phytoplankton community structure, exhibiting lower phytoplankton abundance, Dia/Dino index, and species richness in the cold water mass region, where adaptable species such as Tripos muelleri and Paralia sulcata predominated. Our results emphasized the impact of environmental changes associated with climate change, including rising temperatures, increased salinity, and enhanced stratification, on the phytoplankton community structure in recent years, particularly concerning the dominant species composition and the Dia/Dino index. Therefore, ongoing attention to the effects of climate change on coastal environments and phytoplankton communities is essential.

An enhancer–promoter-transcription factor module orchestrates plant immune homeostasis by constraining camalexin biosynthesis - Ying Zhang; Meng Tang; Yi Zhang; Qinglin Cheng; Lijiang Liu; Wei Chen; Jiatao Xie; Jiasen Cheng; Yanping Fu; Bo Li; Daohong Jiang; Xiao Yu (Molecular Plant, 2025)

Salicylic acid cooperates with different small molecules to control biotic and abiotic stress responses - Kexing Xin; Yining Wu; Aziz Ul Ikram; Yanping Jing; Shan Liu; Yawen Zhang; Jian Chen (Journal of Plant Physiology, 2025)

Phosphorus-oxygen modified anthracene-based emitters for high-efficiency deep-blue OLEDs approaching the BT.2020 blue standard - Ruicheng Wang; Yihong Zhu; Dehua Hu; Jie Hu; Si-wei Chen; Jieying Lin; Longjiang Xing; Yanping Huo; Shaomin Ji (Chemical Engineering Journal, 2025)

Multiple-cation doped LaCl3-based chloride solid-state electrolyte compatible with lithium metal - Xuxia Hao; Kai Chen; Min Jiang; Yanping Tang; Yuexin Liu; Kefeng Cai (Chemical Engineering Journal, 2025)

Bisulfite-free detection of DNA methylation in early-stage lung cancer with a multiplex SERS immunoassay - Dechan Lu; Yanping Chen; Longfeng Ke; Zufang Huang; Yudong Lu; Jing Wang (Chemical Engineering Journal, 2025)

Highly degradable bio-based plastic with water-assisted shaping process and exceptional mechanical properties - Jingjing Wang; Yuan Liang; Yuhan Chen; Hai Wan; Wenbin Jin; Ting Luo; Yuwei Chen; Peng Wei; Shuohan Huang; Yong He; Yanping Wang; Yumin Xia (Carbohydrate Polymers, 2025)

Two paths, one goal: mechanism of calcium homeostasis to balance plant growth and immunity - Aziz Ul Ikram; Yanping Jing; Huan Chen; Jian Chen (Science China Life Sciences, 2025)

Anti-inflammatory, anti-colitis, and antioxidant effects of columbianadin against DSS-induced ulcerative colitis in rats via alteration of HO-1/Nrf2 and TLR4-NF-κB signaling pathway - Yanping Zhang; Ping Cao; Dongyuan Qin; Ying Zhao; Xing Chen; Peng Ma (Inflammopharmacology, 2025)

Effects of cloprostenol and oxytocin on ultrasonographic changes of uterine horns in postpartum primiparous Hu sheep - Yixuan Li; Zongling Liu; Wenqian Zhang; Chunhao Zhu; Xi Chen; Yukun Zhao; Lei Liu; Ting Ting Zhu; Mingyang Geng; Yanping Wang; Weibin Zeng (Animal Reproduction Science, 2025)

Monoclonal antibody development and antigenic epitope identification of infectious bursal disease virus VP5 - Jinze Han; Xinxin Niu; Chengfei Ge; Ziwen Wu; Guodong Wang; Mengmeng Huang; Yulong Zhang; Runhang Liu; Mengmeng Xu; Hangbo Yu; Jingzhe Han; Suyan Wang; et al. (The Veterinary Journal, 2024)

Research on parametric roll of the polar environmental transport ship based on time-domain Rankine panel method - Wei Zhang; Yadong Liu; Yanping He; Yan Zhou; Dong Wang; Yuying Tang; Jianmei Chen (Ocean Engineering, 2024)

A solar thermoelectric system by temperature difference for efficient removal of chromium (VI) in water and soil - Dongqing Cai; Rongxi Hu; Minxue Guo; Dongfang Wang; Yanping Zhu; Chen Sun; Xinyan Chen; Jinghong Ye; Xianghai Kong; He Xu (Journal of Hazardous Materials, 2024)

Insights into the interactions of plant-associated bacteria and their role in the transfer of antibiotic resistance genes from soil to plant - Yanping Shen; Baiyu Zhang; Ye Yao; Hanbo Wang; Zhilu Chen; Anjing Hao; Ping Guo (Journal of Hazardous Materials, 2024)

Characterization of the key odorants in goji wines in three levels of sweetness by applications of sensomics approach - Yan Zheng; Claudia Oellig; Youfeng Zhang; Yuan Liu; Yanping Chen; Yanyan Zhang (Food Chemistry, 2024)

A study on the structure-functionality relationship of Solenaia oleivora protein under high-intensity ultrasonication processing - Wanwen Chen; Wu Jin; Xueyan Ma; Haibo Wen; Yanping Li; Gangchun Xu; Pao Xu; Hao Cheng (Food Chemistry, 2024)

Characteristics of volatile organic compounds under different operating conditions in a petrochemical industrial zone and their effects on ozone formation - Yanping Yang; Xianhong Meng; Qiang Chen; Qiang Xue; Lina Wang; Jian Sun; Wenkai Guo; Huijie Tao; Lili Yang; Feifei Chen (Environmental Pollution, 2024)

Effects of valley topography on ozone pollution in the Lanzhou valley: A numerical case study - Wenkai Guo; Yanping Yang; Junke Zhang; Keran Han; Yinhua Yang; Qiang Chen; Shixue Li; Yuhuan Zhu (Environmental Pollution, 2024)

Protonated polyethyleneimine enables synchronous crosslinking of polyimide nanofiltration membranes for dye desalination - Qing Fang; Sudan Lan; Xiuxiu Mu; Yanping Zhang; Ya Li; Yajuan Wang; Lihui Yao; Yuyun Chen; Dan Qiu; Linghui Wang (Desalination, 2024)

Construction of structure-matching In-Ni catalysts for the selective hydrogenation of α-methylacrolein - Lin Ai; Yanping Chen; Fang Lu; Jiaxu Liu; Xiao-Feng Wu; Shengjun Huang (Chemical Engineering Journal, 2024)

A prediction method for favorable hydrocarbon accumulation areas in carbonate oil reservoirs based on machine learning and driven by formation water chemical characteristic data - Zhiwei Chen; Jianbo Gao; Hong Pang; Zhipeng Huo; Ningliang Sun; Yanping Lv; Yan Wang; Bo Wu (Carbonates and Evaporites, 2024)

Sedimentary dynamics in southern Mariana Trench and its controlling factors in past 440 kyr - Zhongshan Shen; Haifeng Wang; Yanping Chen; Yun Cai; Liang Yi (Frontiers in Marine Science, 2024)
Understanding sediment dynamics and their controlling factors is essential for Quaternary studies, yet they remain poorly documented in the Mariana Trench. In this work, we examine this basic character from a sediment core collected at a depth of 6470 m from the southern part of the Mariana Trench, documenting changes in sedimentary dynamics over the past ~440 kyr. Our primary findings are as follows: (1) The median grain size is 13.6 ± 12.0 μm, and minimal changes in clay (30.9 ± 9.4%) and silt (56.6 ± 4.0%) contents, indicating a low-dynamic depositional environment; (2) Three grain-size components were identified, characterized by modal changes of ~4/60 μm, ~20 μm, and >100 μm. By comparing these results with various environmental proxies, including glacial-interglacial alternations, eolian input, and bottom-water intensity, we suggest that marine productivity has a dominant influence on deep-sea sediment dynamics, though post-depositional processes also contribute. Additionally, topographical conditions and sea-water chemistry appear to be related to the presence of coarse particles, possibly through coarse transport and micro-nodule development. Overall, grain-size parameters provide a valuable investigative tool for understanding the various influences on sediment dynamics in this region.

Evaluating AGS efficiency in PHA synthesis and extraction integrated with nutrient removal: The impact of COD concentrations - Quan Yuan; Song Chen; Yun Chen; Xinyu Zhang; Yuqing Lou; Xueting Li; Qian Liang; Yanping Zhang; Yingxue Sun (Chemosphere, 2024)

Recombinant Marek’s disease virus type 1 provides full protection against H9N2 influenza A virus in chickens - Yuntong Chen; Qingqing Yu; Wenrui Fan; Xianying Zeng; Zibo Zhang; Guobin Tian; Changjun Liu; Hongmei Bao; Longbo Wu; Yanping Zhang; Yongzhen Liu; Suyan Wang; et al. (Veterinary Microbiology, 2024)

Mobilization of phosphorus in sediments of eutrophic lakes induced by elevated sulfate levels - Lanqing Zhang; Miaotong Yu; Simin Yu; Huaizhi Chen; Mengmeng Xiao; Guoxiang Wang; Yanping Zhao (Science of The Total Environment, 2024)

Sustainable upcycling of copper from waste printed circuit boards with the assistance of tannic acid and Fe3+ to a magnetic heterogeneous catalyst - Yanping Zhong; Sisi Hu; Jinghua Xu; Zhenguo Chen; Shuhua Wang (Journal of Environmental Management, 2024)

Uncovering the Shuixian tea grades hierarchy in Chinese national standard: From sensory evaluation to microstructure and volatile compounds analysis - Yanping Lin; Yibiao Huang; Xia Liu; Yani Pan; Xinyu Feng; Haowei Guo; Xiaolan Li; Yike Tao; Ping Chen; Qiang Chu (Food Chemistry, 2024)

Rapid redox-response featured visual ascorbic acid sensor based on simple-assembled europium metal-organic framework - Lin-Lin Zhang; Li Li; Dan Wang; Yanping Hong; Kaijie Tang; Jiaxin Hong; Zeng Chen; Wuying Yang; Limin Lu; Lu-Ying Duan (Food Chemistry, 2024)

Enhancing FRP-concrete interface bearing capacity prediction with explainable machine learning: A feature engineering approach and SHAP analysis - Yanping Zhu; Woubishet Zewdu Taffese; Genda Chen (Engineering Structures, 2024)

Multi-drug loaded electrospinning nanofibers promote healing with less scar formation by remodeling wound microenvironment via modulating TGF-β1/Smads/EN1 signal - Xiaoyan Zeng; Zhenfeng Guan; Reyisha Yusufu; Siyi Li; Qi WU; Yanping Feng; Tiantian Chen; Muxiang Luo; Fenghuan Wei (Chemical Engineering Journal, 2024)

Dynamic of phytoplankton community during varying intensities of the northeast monsoon in the Taiwan Strait - Yanping Zhong; Peixuan Wang; Jinxin Chen; Xin Liu; Edward A. Laws; Bangqin Huang (Acta Oceanologica Sinica, 2024)

Early diagenesis, sedimentary dynamics and metal enrichment reveal deep-sea ventilation in Magellan Seamounts during the middle Pleistocene - Zhongshan Shen; Yanping Chen; Pavel Mikhailik; Yun Cai; Haifeng Wang; Liang Yi (Frontiers in Marine Science, 2024)
Seamounts are ubiquitous topographic units in the global oceans, and the Caiwei Guyot in the Magellan Seamounts of the western Pacific is a prime example. In this study, we analyzed a well-dated sediment core using magnetic properties, sediment grain size, and metal enrichment to uncover regional ventilation history during the middle Pleistocene and explore potential linkages to global climate changes. Our principal findings are as follows: (1) The median grain size is 3.3 ± 0.2 μm, and clay and silt particles exhibit minimal variation, with average values of 52.8 ± 1.8% and 38.2 ± 1.6%, respectively, indicating a low-dynamic process; (2) Three grain-size components are identified, characterized by modal patterns of ~3 μm (major one), ~40 μm, and 400–500 μm, respectively; (3) Magnetic coercivity of the deep-sea sediments can be classified into three subgroups, and their coercivity values are 6.1 ± 0.5 mT, 25.7 ± 1.0 mT, and 65.2 ± 2.1 mT. Based on these results, we propose a close linkage between magnetic coercivity and metal enrichment, correlating with changes in deep-sea circulation intensity. Conversely, sediment grain-size changes seem to be more strongly influenced by eolian inputs. Consequently, we suggest that regional ventilation has weakened since ~430 ka, likely linked to a reduction in Antarctic bottom water formation.

Prediction and empirical formula correction for brash ice resistance using CFD-DEM based on invisible bulbous bow ship - Jianmei Chen; Zhe Chen; Dong Wang; Yuqing Zhang; Yanping He (Ocean Engineering, 2024)

Efficient and environmentally friendly uric acid voltametric sensor based on Ni-MOF and carboxylated multi-walled carbon nanotubes nanocomposites - Aiting Chen; Nana Tang; Yanping Wei; Shuting Shi; Chuanqin Zhou; Quanguo He; Jianhua Ding (Journal of Environmental Chemical Engineering, 2024)

Quinary metal oxide NiCoMnCeCaOx nanorod as a multifunctional catalyst towards hydrogen production from ethanol steam reforming: Synergistic effect of polymetallic component - Mingzheng Liao; Chunrun Qin; Liujie Xu; Sihan Guo; Chao Wang; Yi Li; Wei Liu; Qingbin Song; Ying Chen; Yanping Du (Chemical Engineering Journal, 2024)

Understandings in surface metal exsolution of NiFeZn ternary alloy/spinel in ethanol steam reforming: The key to hydrogen production - Mingzheng Liao; Wei Liu; Congkang Li; Sihan Guo; Yanyu Chen; Chao Wang; Ying Chen; Yanping Du (Chemical Engineering Journal, 2024)

Heterostructure-anchored 3D CNT-bridged graphene architecture via layer-by-layer structural engineering for thick electrodes of supercapacitors - Yanping Song; Nian Li; Jun Kang; Zhao Li; Na Hong; Shuai Han; Liqing Chen; Shudong Zhang; Cui Liu; Congfa Song; Jiakuan Zhang; Zhenyang Wang (Chemical Engineering Journal, 2024)

Cellular Senescence-Related Long Non-coding RNA Signatures Predict Prognosis in Juvenile Osteosarcoma - Peng Zhao; Junli Chang; YeKai Chen; Xingyuan Sun; Xiaoping Ma; Chujie Zhou; Lei Zhou; Yongjun Wang; Yanping Yang (Phenomics, 2024)
Osteosarcoma is the most common malignant bone tumor and is frequently diagnosed in juvenile. Cellular senescence is a fundamental hallmark of osteosarcoma and plays a vital role in the initiation and progression of aging and tumorigenesis. Long non-coding RNAs (lncRNAs) are implicated in tumorigenesis. In this study, six cellular senescence-related lncRNAs with independent prognostic significance in juvenile osteosarcoma patients were identified through univariate Cox regression analysis, least absolute shrinkage and selection operator (LASSO) regression analysis, and multivariate Cox regression analysis. Prognostic significance was further confirmed by Kaplan–Meier (KM) survival curves, co-expression interaction networks, and sankey diagrams. A prognostic model of cellular senescence-related genes in juvenile osteosarcoma patients was then constructed using multivariate Cox regression analysis based on these six genes. High- and low-risk groups were identified according to the median risk score calculated by the prognostic model. The favorable prognostic significance of this model was demonstrated through survival curves, receiver operating characteristic (ROC) curves, distribution scatter plots and lncRNA expression heatmaps. Furthermore, cellular senescence-related lncRNAs were validated by enrichment analysis, immunological correlation analysis, m 6 A correlation analysis, and drug sensitivity correlation analysis. These findings are important for improving the prognosis of juvenile osteosarcoma patients and understanding the mechanisms underlying cellular senescence in juvenile osteosarcoma development.

Ginsenoside Rg1 treats chronic heart failure by downregulating ERK1/2 protein phosphorylation - Liqi Peng; Shaodong Li; Huzhi Cai; Xueliang Chen; Yanping Tang (In Vitro Cellular & Developmental Biology - Animal, 2024)

Bi-allelic missense variants in MEI4 cause preimplantation embryonic arrest and female infertility - Zhiqi Pan; Weijie Wang; Ling Wu; Zhongyuan Yao; Wenjing Wang; Yao Chen; Hao Gu; Jie Dong; Jian Mu; Zhihua Zhang; Jing Fu; Qiaoli Li; et al. (Human Genetics, 2024)

Numerical simulation on staggered grids of three-dimensional brinkman-forchheimer flow and heat transfer in porous media - Wei Liu; Yingxue Song; Yanping Chen; Gexian Fan; Pengshan Wang; Kai Li (Computational Geosciences, 2024)

Screening of promising molecules against potential drug targets in Yersinia pestis by integrative pan and subtractive genomics, docking and simulation approach - Lei Chen; Lihu Zhang; Yanping Li; Liang Qiao; Suresh Kumar (Archives of Microbiology, 2024)

Response of phytoplankton communities to environmental changes in the Bohai Sea in late summer (2011–2020) - Yibo Wang; Zhiliang Liu; Yanping Qi; Xiao Chen; Yang Chen; Du Su; Xiaobo Yuan; James Klippel-Cooper (Acta Oceanologica Sinica, 2024)

Effect of long-term dosage of hydrazine on mainstream anammox process: Biofilm characteristics and microbial community - Quan Yuan; Yuqing Lou; Song Chen; Yun Chen; Xueting Li; Xinyu Zhang; Liang Qian; Yanping Zhang; Yingxue Sun (Chemosphere, 2024)

The effects of queen mandibular pheromone on Nosema (Vairimorpha) ceranae infections in caged honey bees - Wei-Fone Huang; Ama Safo-Mensa; Evan Palmer-Young; Jay D. Evans; Yanping Chen (Journal of Invertebrate Pathology, 2024)

Understanding the variability of ground-level ozone and fine particulate matter over the Tibetan plateau with data-driven approach - Haobin Zhong; Ling Zhen; Lin Yang; Chunshui Lin; Qiufang Yao; Yanping Xiao; Qi Xu; Jinsong Liu; Baihua Chen; Haiyan Ni; Wei Xu (Journal of Hazardous Materials, 2024)

High recoverable energy storage density and efficiency achieved in doped NaNbO3 ceramics via composition design strategy for pulsed power capacitor - Renkai Zhao; Kaiyuan Wang; Wenhua Li; Yujia Yuan; Xingui Tang; Jia Hu; HuaXiang Fan; Kaijie Chen; Wanglai Song; Yanping Jiang; Xiaobing Guo (Chemical Engineering Journal, 2024)

Antidepressant effects of activation of infralimbic cortex via upregulation of BDNF and β-catenin in an estradiol withdrawal model - Jiali Chen; Yiying Zhou; Miaojun Lai; Yanping Zhang; Yifang Hu; Dingding Zhuang; Wenhua Zhou; Yisheng Zhang (Psychopharmacology, 2024)
Rationale Clinical and preclinical studies have demonstrated that estradiol withdrawal after delivery is one of important factors involved in the pathogenesis of postpartum depression (PPD). The infralimbic cortex (IL) is related to anxiety and mood disorders. Whether IL neurons mediate PPD is still unclear. Objectives This study was to observe the antidepressant effect and expression of BDNF and β-catenin in IL by allopregnanolone (ALLO) treatment or the selective activation or inhibition of IL neurons using a chemogenetic approach in a pseudopregnancy model of PPD. Methods Administration of estradiol combined with progesterone and the abrupt withdrawal of estradiol simulated the pregnancy and early postpartum periods to induce depression in ovariectomized rats. The relative expression levels of β-catenin and BDNF were observed by western blotting. Results Immobility time was significantly increased in the forced swim test and open-arm movement was reduced in the elevated plus maze test in the estradiol-withdrawn rats. After ALLO treatment, the immobility time were lower and open-arm traveling times higher than those of the estradiol-withdrawn rats. Meanwhile, the expression level of BDNF or β-catenin in the IL was reduced significantly in estradiol-withdrawn rats, which was prevented by treatment with ALLO. The hM3Dq chemogenetic activation of pyramidal neurons in the IL reversed the immobility and open-arm travel time trends in the estradiol-withdrawal rat model, but chemogenetic inhibition of IL neurons failed to affect this. Upregulated BDNF and β-catenin expression and increased c-Fos in the basolateral amygdala were found following IL neuron excitation in model rats. Conclusions Our results demonstrated that pseudopregnancy and estradiol withdrawal produced depressive-like behavior and anxiety. ALLO treatment or specific excitement of IL pyramidal neurons relieved abnormal behaviors and upregulated BDNF and β-catenin expression in the IL in the PPD model, suggesting that hypofunction of IL neurons may be involved in the pathogenesis of PPD.

A numerical method for two-dimensional transient nonlinear convection-diffusion equations - Xiangyuan Meng; Mei Huang; Boxue Wang; Xiaoping Ouyang; Yanping Huang; Denggao Chen; Yanting Cheng; Yaodi Li (Annals of Nuclear Energy, 2024)

Spatial heterogeneity and driving mechanisms of carbon storage in the urban agglomeration within complex terrain: Multi-scale analyses under localized SSP-RCP narratives - Hongyi Zhang; Xin Li; Yanping Luo; Lu Chen; Minxi Wang (Sustainable Cities and Society, 2024)

N-acyl homoserine lactones (AHLs) enhanced removal of cadmium and other pollutants by algae-bacteria consortia - Qingnan Yu; Jiale Chen; Menglei Ye; Yanping Wei; Chunhua Zhang; Ying Ge (Journal of Environmental Management, 2024)

Simultaneous removal of tetracycline hydrochloride and hexavalent chromium by heterogeneous Fenton in a photocatalytic fuel cell system - Jinghong Ye; He Xu; Xianghai Kong; Yong Zhang; Yuhan Chen; Benji Zhou; Yanping Zhu; Dongqing Cai; Dongfang Wang (Journal of Environmental Management, 2024)

Potential modulation strategy on bismuth vanadate-based semiconductor to enhance antibiotic degradation in heterogeneous electro-Fenton system - Jinghui Pan; Zimu Zhang; Zuofang Yao; Songyu Fan; Tingting Zhu; Chenchen Xing; Yujia Liu; Jianhua Chen; Hongxiang Zhu; Yanping Hou; Shuangfei Wang (Chemical Engineering Journal, 2024)

Effect of Sulfate and Acid Orange 7 on Sb(V) Removal by Anaerobic Granular Sludge: Role of Granular Activated Carbon - Qi Li; Yanping Zhu; Yanbiao Liu; Xiaoguang Chen; Nan Jiang; Mengying Yan; Xuhua Li; Haoyu Xing; Yinzhou Bao; Manhong Huang (Water, Air, & Soil Pollution, 2024)

A highly sensitive SERS substrate of porous membrane-Ag NPs for kidney cancer detection - Sheng Chen; Jiamin Gao; Hongyi Zhang; Li Liu; Feng Lin; Zaijun Cheng; Yanping Chen; Dongyu Guo; Xingen Gao; Juqiang Lin (Analytica Chimica Acta, 2024)

Novel insight into the formation and improvement mechanism of physical property in fermented tilapia sausage by cooperative fermentation of newly isolated lactic acid bacteria based on microbial contribution - Qiaoyan Cui; Laihao Li; Hui Huang; Yanping Yang; Shengjun Chen; Chunsheng Li (Food Research International, 2024)

A newly-discovered tea population variety processed Bai Mu Dan white tea: Flavor characteristics and chemical basis - Yanping Lin; Yibiao Huang; Su Zhou; Xiaolan Li; Yike Tao; Yani Pan; Xinyu Feng; Haowei Guo; Ping Chen; Qiang Chu (Food Chemistry, 2024)

Chiral dual-core emitters based-on through-space coupling for high-performance OLEDs with little efficiency roll-off - Lifen Chen; Mingjia Deng; Shao-Yun Yin; Yu Fu; Yingxiao Mu; Jia-Xiong Chen; Lingyun Cui; Shaomin Ji; Yanping Huo; Hao-Li Zhang (Chemical Engineering Journal, 2024)

Knocking out Selenium Binding Protein 1 Induces Depressive-Like Behavior in Mice - Yi Jia; Xin Zhang; Yongmei Wang; Yang Liu; Jie Dai; Liangliang Zhang; Xian Wu; Jie Zhang; Hongxi Xiang; Yanping Yang; Zhu Zeng; Yulian Chen (Biological Trace Element Research, 2024)

Loop PDE of viral capsid protein is involved in immune escape of the emerging novel variant infectious bursal disease virus - Guodong Wang; Nan Jiang; Hangbo Yu; Xinxin Niu; Mengmeng Huang; Yulong Zhang; Wenying Zhang; Jinze Han; Mengmeng Xu; Runhang Liu; Ziwen Wu; Jingzhe Han; et al. (Veterinary Microbiology, 2024)

Bacteria deploy water channels to aid infection in plants - Aziz Ul Ikram; Yanping Jing; Huan Chen; Jian Chen (Trends in Plant Science, 2024)

Enhanced Sb(V) removal of sulfate-rich wastewater by anaerobic granular sludge assisted with Fe/C amendment - Qi Li; Yanping Zhu; Nan Jiang; Jun Li; Yanbiao Liu; Xiaoguang Chen; Xiaoyang Xu; Huangyingzi Wang; Yimeng Ma; Manhong Huang (Science of The Total Environment, 2024)

Research on leaching behavior of manganese and ammonia nitrogen in electrolytic manganese residue under oxalic acid/hydrogen peroxide system - Chenxin Sun; Yu Zhang; Yanping Yang; Qian Shang; Yunqiu Liu; Qianlin Chen (Journal of Water Process Engineering, 2024)

Gold-copper-doped lanthanide luminescent metal-organic backbone induced self-enhanced molecularly imprinted ECL sensors for ultra-sensitive detection of chlorpyrifos - Yishan Fang; Yanping Li; Xufeng Zang; Yingxue Chen; Xinran Wang; Na Wang; Xiangying Meng; Bo Cui (Food Chemistry, 2024)

Electron transfer mediated photo-Fenton-like synergistic catalysis of Fe,Cu-doped MIL-101 coupled with Ag3PO4: Quantitative evaluation and DFT calculations - Xiaojuan Chen; Liang Yao; Song Xu; Juhua He; Ning Li; Jiaxin Li; Bin Liu; Yanping Zhu; Xin Chen; Hailong Wang; Runliang Zhu (Environmental Pollution, 2024)

Mitochondria targeting photoredox catalyst-induced pyroptosis for enhanced immunotherapy against hypoxic tumor cells - Yanping Wu; Qingsong Liu; Shumeng Li; Wenhao Yu; Huanhuan Fan; Shankun Yao; Weijiang He; Zijian Guo; Yuncong Chen (Chemical Engineering Journal, 2024)

Multifunctional Ac@ZIF-8/AgNPs nanoplatform with pH-responsive and ROS scavenging antibacterial properties promotes infected wound healing - Yipeng Pang; Maofang Zhao; Yuhan Xie; Yanping Wang; Yuxin You; Yongding Ke; Chaoyi Zhang; Xiaohan Chen; Yijia Yang; Chunlei Zhang; Xi Chen; Yi Liu; et al. (Chemical Engineering Journal, 2024)

Sequence and epigenetic variations of R2R3-MYB transcription factors determine the diversity of taproot skin and flesh colors in different cultivated types of radish (Raphanus sativus L.) - Qingbiao Wang; Yanping Wang; Xiangyu Wu; Wenyu Shi; Ningjie Chen; Yuanting Pang; Li Zhang (Theoretical and Applied Genetics, 2024)

Phytoplankton community responses to the combined effects of internal waves and anticyclonic eddies shed from the Kuroshio intrusion - Yanping Zhong; Xiaolin Bai; Edward A. Laws; Wenfang Lu; Zhida Huang; Wupeng Xiao; Jixin Chen; Lingqi Ma; Xin Liu; Bangqin Huang (Ocean Dynamics, 2024)

A within-subject voxel-wise constant-block partial least squares correlation method to explore MRI-based brain structure–function relationship - Xiaoyu Zhao; Kewei Chen; Hailing Wang; Yufei Gao; Xiangmin Ji; Yanping Li (Cognitive Neurodynamics, 2024)

New insights into functional divergence and adaptive evolution of uncultured bacteria in anammox community by complete genome-centric analysis - Yi-Cheng Wang; Yanping Mao; Hui-Min Fu; Jin Wang; Xun Weng; Zi-Hao Liu; Xiao-Wei Xu; Peng Yan; Fang Fang; Jin-Song Guo; Yu Shen; You-Peng Chen (Science of The Total Environment, 2024)

The impact of microbial inoculants on large-scale composting of straw and manure under natural low-temperature conditions - Yanping Wang; Qi Yu; Chuang Zheng; Yanbo Wang; Heshu Chen; Shijia Dong; Xiaomei Hu (Bioresource Technology, 2024)

Understanding the variable metal concentrations in estuarine oysters Crassostrea hongkongensis: A biokinetic analysis - Shaomei Yang; Yanping Li; Fengyuan Chen; Shanshan Chen; Xin Luo; Wei Duan; Yongyan Liao; Hao Jiang; Ke Pan (Marine Environmental Research, 2024)

Ensemble-learning model based ultimate moment prediction of reinforced concrete members strengthened by UHPC - Woubishet Zewdu Taffese; Yanping Zhu; Genda Chen (Engineering Structures, 2024)

Aralianudaside A, an unusual skeleton triterpenoid saponin with anti-airway inflammatory activity from Aralia elata - Pengcheng Yin; Haishan Qian; Shaohua Li; Benqin Tang; Juan Wang; Shuai Chen; Guanghui Ni; Fawu Dong; Yanping Li; Feng Huang; Rongping Zhang; Hongping He; et al. (Natural Product Research, 2024)

Farmed Chinese Perch (Siniperca chuatsi) Coinfected with Parasites and Oomycete Pathogens - Xiandong Xu; Yanping Zhang; Liyun Ding; Jiangfeng Huang; Zhiyong Zhou; Wenjing Chen (Fishes, 2024)
Farming Chinese perch in aquaculture systems with artificial diets is a new method and developing trend. This method of raising Chinese perch has led to outbreaks of new diseases. In 2022, a disease outbreak occurred among farmed Chinese perch fed an artificial diet in Jiangxi Province, China, during which 50% of the fish died. The clinical signs exhibited by the diseased Chinese perch included decreased physical vitality, anorexia, emaciation, and dorsal fin ulceration with white cysts and flocs. Coinfection with ciliate parasites and an oomycete was found. No pathogenic bacteria were isolated from the microbial test, and the viral detection results were negative. After morphological and 18S or 28S rDNA sequence clustering analysis, the parasites were identified as Epistylis wuhanensis and Zoothamnium sp., while the oomycete was identified as Achlya klebsiana. This article discusses the interaction between parasitic and oomycete coinfections in Chinese perch from the perspective of the characteristics of Chinese perch raised with an artificial diet. The relationships between parasites, oomycete, and fish were also briefly discussed. This is the first report of the coinfection of Chinese perch with Epistylis wuhanensis, Zoothamnium sp. and Achlya klebsiana.

Vascular plant communities and biocrusts act as controlling factors in mitigating soil erosion on the Great Wall in a semi-humid area of Northwestern China - Yanping Liu; Rongliang Jia; Wanfu Wang; Yuchen Wan; Yanhong Gao; Hongtao Zhan; Jing Ren; Zhang Chen; Fei Qiu; Jing Zhu (Science of The Total Environment, 2024)

Understanding the spatial and seasonal variation of the ground-level ozone in Southeast China with an interpretable machine learning and multi-source remote sensing - Haobin Zhong; Ling Zhen; Qiufang Yao; Yanping Xiao; Jinsong Liu; Baihua Chen; Wei Xu (Science of The Total Environment, 2024)

Honeybee symbiont Bombella apis could restore larval-to-pupal transition disrupted by antibiotic treatment - Chen Xiaowen; Li Jiahao; Ding Zhaorun; Li Wenfeng; Han Richou; Chen Yanping; Xie Huichun; Zhang Yi (Journal of Insect Physiology, 2024)

High voltage, toughness and improved interfacial ion deposition through a dual-crosslinked and self-healable hydrogel electrolyte for green zinc-ion batteries - Yanping Yang; Luwei Shi; Yaqi Wu; Zhehua Chen; Xinyuan Zhu; Lijun Du; Youfu Wang (Chemical Engineering Journal, 2024)

Rational design and fabricate of protonated crosslinked chitosan adsorbent for boosting the removal of nitrite in water - Wenbin Chen; Yanping Feng; Xiaoming Wang; Chenchen Zhang; Suyao Liu; Yibing Song; Yiwen Fang (Chemical Engineering Journal, 2024)

Dual-Coordinated atomically dispersed Pt nanozymes evoke efficient pyroptosis for cancer immunotherapy - Jingqi Chen; Yanping Tang; Yan Lin; Xiuxin Lu; Lineng Wei; Shiyu Xia; Wenxin Niu; Weizhong Tang; Weiqing Zhang (Chemical Engineering Journal, 2024)

Detection of two homologous major QTLs and development of diagnostic molecular markers for sucrose content in peanut - Zhihui Wang; Yue Zhang; Dongxin Huai; Yuning Chen; Xin Wang; Yanping Kang; Liying Yan; Huifang Jiang; Kede Liu; Yong Lei; Boshou Liao (Theoretical and Applied Genetics, 2024)

Measurement, influencing factors and prediction on carbon emission performance of countries along the Belt and Road - Jing Li; Yanping Zhou; Huiying Chen (Clean Technologies and Environmental Policy, 2024)

SlCNR regulates postharvest water loss and wax accumulation in tomato fruit and directly represses the transcription of very-long-chain (VLC) alkane biosynthesis-related genes SlCER1-2 and SlCER6 - Di Chen; Tingyu Wang; Hua Huang; Qiaoli Zhang; Xue Chen; Zongyan Sun; Yanping Song; Yuetong Yi; Chengxia Liu; Donald Grierson; Jiankang Cao; Daqi Fu; et al. (Postharvest Biology and Technology, 2024)

Ecological risk assessment of the typical anti-epidemic drugs in the Pearl River Delta by tracing their source and residual characteristics - Huazhi Wu; Liying Bin; Pengran Guo; Yanping Zhao; Chao Chen; Zhiliang Chen; Bing Tang (Journal of Hazardous Materials, 2024)

A Novel N Self-Doped Porous Biochar Synthesized by KHCO3-Activated Chicken Feather for the Remediation of Tetracycline-Contaminated Water and Soil - Yu Deng; Jingfan Chen; Zhidan Xiao; Jiaying Liu; Jie Zhang; Bingqi Zhu; Xiaotong You; Fuquan Ni; Tianqi Ao; Yanping Tan (Water, Air, & Soil Pollution, 2024)

Identification of QTLs associated with very-long chain fatty acid (VLCFA) content via linkage mapping and BSA-seq in peanut - Xiaomeng Xue; Jianguo Li; Jie Wu; Meiling Hu; Nian Liu; Liying Yan; Yuning Chen; Xin Wang; Yanping Kang; Zhihui Wang; Huifang Jiang; Yong Lei; et al. (Theoretical and Applied Genetics, 2024)

Molecularly imprinted polymer sheathed mesoporous silica tube as SPME fiber coating for determination of tobacco-specific nitrosamines in water - Yuemei Chen; Yang Yu; Shaohan Wang; Jiajia Han; Mengge Fan; Yanping Zhao; Junlang Qiu; Xin Yang; Fang Zhu; Gangfeng Ouyang (Science of The Total Environment, 2024)

Two-stage method recovery of metals from copper slag: Realize the resource utilization of all components - Lanbin Wang; Yangming Xu; Liang Tian; Yu Chen; Anju Yang; Guixiang Gan; Yanping Ma; Yaguang Du (Minerals Engineering, 2024)

Impact of cobalt recycling on China's electrification process: Assessing the potential reduction in cobalt demand from battery recycling - Lilong Chen; Xin Li; Yanping Luo; Wenli Tan; Qiaoying Ma; Minxi Wang; Jianbo Yang (Journal of Cleaner Production, 2024)

Fully space-confined donor-acceptor interaction for highly efficient thermally activated delayed fluorescence emitters - Wen-Cheng Chen; Ming-Hui Zheng; Yu-Lan Wu; Ru-Jia Wang; Jia-Ming Jin; Si-Wei Chen; Bo Liu; Jia-Xiong Chen; Yanping Huo; Shaomin Ji (Chemical Engineering Journal, 2024)

A multifunctional emitter with synergistical adjustment of rigidity and flexibility for high-performance data-recording and organic light-emitting devices with “hot exciton” channel - Guowei Chen; Wen-Cheng Chen; Yaozu Su; Ruicheng Wang; Jia-Ming Jin; Hui Liang; Bingxue Tan; Dehua Hu; Shaomin Ji; Hao-Li Zhang; Yanping Huo; Yuguang Ma (Chemical Engineering Journal, 2024)

Testing a biocontrol agent consortium for suppression of tomato bacterial wilt through rhizosphere microecological regulation - Xuefang Zheng; Jieping Wang; Meichun Chen; Yanping Chen; Zheng Chen; MingKuang Wang; Bo Liu (Applied Soil Ecology, 2024)

Miniaturized ascorbic acid assay platform based on point discharge atomic emission spectrometry coupling with gold filament enrichment - Yanping Wang; Yuemei Chen; Kejun Li; Jinrong Zhou; Xin Yuan; Mei Zhang; Ke Huang (Analytica Chimica Acta, 2024)

Impact of facemask debris on marine diatoms: Physiology, surface properties, sinking rate, and copepod ingestion - Fengyuan Chen; Zhen Zhang; Yanping Li; Hao Jiang; Yanfei Zhou; Hongbin Liu; Ke Pan; Jie Ma (Science of The Total Environment, 2023)

Engineering redirected NF-κB/OIP5 expression programs to enhance tumor responses to chemotherapy in bladder cancer - Binbin Zheng; Liman Niu; Haibo Xu; Yubin Yang; Yanping Chen; Chenguang Wang; Wei Chen; Weiren Huang (Science Bulletin, 2023)

Proportion of dead cells in phytoplankton modulates community structure - Peixuan Wang; Edward A. Laws; Xin Liu; Jixin Chen; Yanping Zhong; Chao Xu; Bangqin Huang (Progress in Oceanography, 2023)

Gas-expanded pore MOF derived Sm/MnOx catalysts enable ultralow-temperature selective catalytic reduction of NOx - Shengchen Li; Dan Zhao; Shunli Shi; Fangyu Zhu; Yanping Yang; Shuhua Wang; Shunmin Ding; Chao Chen (Journal of Environmental Chemical Engineering, 2023)

Enhanced nitrogen removal in the upgrading of municipal wastewater treatment plants by using zero-valent iron-modified biofilm carriers and clinoptilolite-modified biofilm carriers - Yanping Shi; Tao Liu; Xie Quan; Shuo Chen; Hongtao Yu; Wuzhe Quan (Chemical Engineering Journal, 2023)

Novel aloe emodin–hydroxyethyl piperazine hybrid dihydrochloride induces oral cancer CAL-27 cells apoptosis through ROS production, DNA damage and mitochondrial pathways - Xing Long; Peilin Yang; Lin Chen; Wen Zhong; Shaofeng Chen; Yanping Li; Shijie Lin; Wei Tian (Medicinal Chemistry Research, 2023)

Co-recovery of Mn and Fe from pyrolusite and copper slag with hydrometallurgy process: Kinetics and leaching mechanisms - Lanbin Wang; Yu Chen; Yangming Xu; Yanping Ma; Yaguang Du (Environmental Science and Pollution Research, 2023)

Microplastic aging alters the adsorption-desorption behaviors of sulfamethoxazole in marine animals: A study in simulated biological liquids - Jiaxuan Li; Yunxue Li; Bushra Maryam; Xiaochen Chen; Yanping Zong; Jianbo Tu; Pingping Zhang; Xianhua Liu (Marine Pollution Bulletin, 2023)

Coupling isotopic signatures and partial extraction method to examine lead pollution in mangrove sediments - Zhenghua Tao; Jian Hu; Qingjun Guo; Rongfei Wei; Linlin Jiao; Yanping Li; Fengyuan Chen; Bailing Fan; Wenlu Lan; Ke Pan (Journal of Hazardous Materials, 2023)

Effective degradation of tetracycline by Pd/AG/ITO electrode: Electrode preparation, characterization, kinetics, degradation mechanism and toxicity assessment - Chen Shao; Jian Zhang; Yuqing Liu; Yuting Jiang; Yanping Jia; Guomin Li; Zhong Sun (Journal of Environmental Chemical Engineering, 2023)

ZIF-8-derived hollow carbon polyhedra with highly accessible single Mn-N6 sites as peroxymonosulfate activators for efficient sulfamethoxazole degradation - Yue Zhao; Rui Gao; He Wang; Yanping Sun; Xiaohui Zhan; Lei Chen; Junyan Liu; Huixiang Shi (Chemical Engineering Journal, 2023)

The built-in electric field and spin-pinning effect in BiVO4/Fe0.4Co0.6Se2/Co(Fe)OxHy for enhanced photoelectrochemical water oxidation - Ben Fan; Ling Ding; Zebin Yu; Ronghua Jiang; Yanping Hou; Shuang Li; Jianhua Chen (Chemical Engineering Journal, 2023)

Hydrothermally treated peat/magnetite composites as highly efficient heterogeneous Fenton catalyst: Integrating multiple reaction mechanisms to enhance the catalytic reactivity for BPA removal - Fangxin Deng; Qingze Chen; Yanping Zhu; Xiaoliang Liang; Runliang Zhu; Yunfei Xi (Chemical Engineering Journal, 2023)

The reverse flow among parallel U-tubes in steam generator under natural circulation condition: A review - Hao Jianli; Ma Junjie; Huang Yanping; Chen Wenzhen; Yu Lei (Annals of Nuclear Energy, 2023)

Effectively synthesized functional Si-doped carbon dots with the applications in tyrosinase detection and lysosomal imaging - Chenfang Miao; Xin Zhou; Xiaoyang Huang; Jiyue Huang; Yanping Chen; Yuebin Liu; Xiaomu Hu; Lingjun Zeng; Shaohuang Weng; Huixing Chen (Analytica Chimica Acta, 2023)

Isotopic signatures unveil the lead sources and migration in surface mangrove sediments - Zhenghua Tao; Guogan Peng; Fengyuan Chen; Qingjun Guo; Rongfei Wei; Jingli Liu; Yanping Li; Hao Jiang; Yongyan Liao; Ke Pan (Science of The Total Environment, 2023)

Detoxification and resource utilization of soda ash chromite ore processing residue by copper slag - Lanbin Wang; Yangming Xu; Yanping Ma; Yu Chen; Anju Yang; Guixiang Gan; Yaguang Du; Yan Sun (Process Safety and Environmental Protection, 2023)

Sentinel supervised lung-on-a-chip: A new environmental toxicology platform for nanoplastic-induced lung injury - Sheng Yang; Tianyi Zhang; Yiling Ge; Yanping Cheng; Lihong Yin; Yuepu Pu; Zaozao Chen; Geyu Liang (Journal of Hazardous Materials, 2023)

Microbial metabolism and humic acid formation in response to enhanced copper and zinc passivation during composting of wine grape pomace and pig manure - Yingchao Zhang; Yang Xu; Xinlong Yu; Jinkang Li; Guang Chen; Shuaijie Wang; Yanping Xu; Rui Xu; Baohai Zhang; Hongqiong Zhang (Bioresource Technology, 2023)

Nitrogen addition regulates the growth of Pinus tabuliformis by changing distribution patterns of endogenous hormones in different organs - Yuhang Peng; Keli Chen; Guoliang Wang; Jiawei Tan; Furong Wei; Yanping Ma (New Forests, 2023)

Exploring the diagnostic value, prognostic value, and biological functions of NPC gene family members in hepatocellular carcinoma based on a multi-omics analysis - Keheng Chen; Xin Zhang; Huixin Peng; Fengdie Huang; Guangyu Sun; Qijiang Xu; Lusheng Liao; Zhiyong Xing; Yanping Zhong; Zhichao Fang; Meihua Liao; Shihua Luo; et al. (Functional & Integrative Genomics, 2023)

Detection of depression marker ASS1 in urine by gold nanoparticles based dual epitope-peptides imprinted sensor - Hong Wei; Zixia Wang; Yanping Wang; Jing Ma; Yan Chen; Min Guo; Yuanyuan Li; Yongling Du; Fangdi Hu (Analytica Chimica Acta, 2023)

Comparison between discarded facemask and common plastic waste on microbial colonization and physiochemical properties during aging in seawater - Jie Ma; Fengyuan Chen; Ciara Chun Chen; Zhen Zhang; Zihan Zhong; Hao Jiang; Junbao Pu; Yanping Li; Ke Pan (Journal of Hazardous Materials, 2023)

A review of metal contamination in seagrasses with an emphasis on metal kinetics and detoxification - Yanping Li; Fengyuan Chen; Ruojing Zhou; Xinqing Zheng; Ke Pan; Guanglong Qiu; Zhongjie Wu; Shiquan Chen; Daoru Wang (Journal of Hazardous Materials, 2023)

A callus-derived regeneration and Agrobacterium-mediated gene transformation developed for bilberry, Vaccinium myrtillus - Yanping Song; Wenbo Luo; Ying Wu; Xiaojie Li; Nick W. Albert; Yinhai Zhang; Xiangtao Chen; Kui Lin-Wang; Cecilia H. Deng; Zhubing Hu; Bingsong Zheng; Xiaofei Wang; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2023)

A novel high-stability bioelectrochemical sensor based on sol-gel immobilization of lactate dehydrogenase and AuNPs-rGO signal enhancement for serum pyruvate detection - Yanping Zhao; Xu Geng; Xiaoling Zhou; Li Xu; Shuai Li; Zhengqiang Li; Yi Guo; Chen Li (Analytica Chimica Acta, 2023)

The integration of the small‐island effect and nestedness pattern - Yanping Wang; Chuanwu Chen; Virginie Millien (Journal of Biogeography, 2023)
Aim The small‐island effect (SIE) and nestedness are two important patterns in the fields of island biogeography and community ecology. However, to date, no study has tried to integrate the SIE and nestedness pattern. Therefore, the aim of this study was to integrate these two biogeographical patterns by proposing a new integrative hypothesis. The integrative hypothesis posits that the degree of nestedness of the large island matrix will be larger than that of the small island matrix split by the threshold of the SIE. Location Global. Taxon Plants, invertebrates and vertebrates. Methods We compiled 219 global datasets with both the presence‐absence matrices and the variables of area and species richness. We also collected six island characteristics influencing the SIE and nestedness patterns, that is island type, taxonomic group, area range, the number of islands, species range and matrix fill. We applied breakpoint regressions to detect SIEs and used the metric NODF (Nestedness metric based on Overlap and Decreasing Fill) to quantify nestedness. We then employed logistic regressions and an information‐theoretic approach to determine which combination of island characteristics was important in determining whether the integrative hypothesis was supported. Results Among the 92 datasets in which SIEs were unambiguously detected, nestedness analyses showed that in 64 cases (69.6%) the values of NODFc (nestedness among sites) for the large island matrices were larger than those of the small island matrices. Matrix fill and area range were substantially important in determining whether the integrative hypothesis was supported. By contrast, island type, taxonomic group, the number of islands and species range received considerably less support. Main Conclusions Our study was the first to integrate the SIE and nestedness pattern. Overall, we found prevalent support for our integrative hypothesis. The integration of the SIE and nestedness provides new and interesting insights into these two biogeographical patterns.

A spatiotemporal deconstruction-based approach for identifying flash drought expansion: Normalized Area-Time Accumulation curve - Ruiqi Chen; Yi Liu; Ye Zhu; Liliang Ren; Yanping Qu; Jason A. Otkin; Vijay P. Singh (Journal of Hydrology, 2023)

Histone modification landscape and the key significance of H3K27me3 in myocardial ischaemia/reperfusion injury - Le Ni; Bowen Lin; Yanping Zhang; Lingjie Hu; Jianghua Lin; Fengmei Fu; Meiting Shen; Can Li; Lei Chen; Jian Yang; Dan Shi; Yi-Han Chen (Science China Life Sciences, 2023)

Molecular cloning, functional characterization and expression of the β-amyrin synthase gene involved in saikosaponin biosynthesis in Bupleurum chinense DC. - Yanping Mao; Hua Chen; Jun Zhao; Yuchan Li; Liang Feng; Yuping Yang; Yiguan Zhang; Ping Wei; Dabin Hou (Journal of Plant Biochemistry and Biotechnology, 2023)

ADGB variants cause asthenozoospermia and male infertility - Ronggui Qu; Zhihua Zhang; Ling Wu; Qun Li; Jian Mu; Lin Zhao; Zheng Yan; Wenjing Wang; Yang Zeng; Ruyi Liu; Jie Dong; Qiaoli Li; et al. (Human Genetics, 2023)

Relationships between Abyssal Redox Conditions and Rock Magnetic Properties of Surficial Sediments in the Western Pacific - Yanping Chen; Dong Xu; Huafeng Qin; Geng Liu; Yibing Li; Weiwei Chen; Liang Yi (Journal of Marine Science and Engineering, 2023)
Reconstructing changes in deep/bottom-water redox conditions are critical for understanding the role of the deep ocean in global carbon and metals cycling; nevertheless, the quantitative relationships between redox proxies and abyssal dissolved oxygen are poorly investigated. In this work, we studied the rock magnetic properties of surficial sediments in the western Pacific to investigate their relationship with regional redox conditions. Our results reveal a consistent sedimentary magnetic mineral assemblage in the western Pacific, dominated by pseudo-single-domain magnetite (Fe3O4), while the ratio of detrital and biogenic magnetite particles in different sites varies substantially. Detailed analyses identified two major magnetic-coercivity components, with modal coercivity values of 13.1 ± 1.6 mT and 54.7 ± 5.3 mT, respectively. All the magnetic parameters we measured, including both concentration-dependent and grainsize-dependent parameters, and the magnetic coercivities, are generally correlated to sedimentary redox conditions; however, the coercivities obtained by mathematical unmixing exhibit a stronger linkage, explaining about a quarter of variance of redox changes. Our findings confirm the potential of magnetic properties for tracing abyssal redox changes in the western Pacific, while the observed magnetic-redox relationships are complex and need further investigation.

An overview of the direct and indirect effects of acid rain on plants: Relationships among acid rain, soil, microorganisms, and plants - Yan Zhang; Jiahong Li; Junyan Tan; Wenbin Li; Bhupinder Pal Singh; Xunan Yang; Nanthi Bolan; Xin Chen; Song Xu; Yanping Bao; Daofei Lv; Anan Peng; et al. (Science of The Total Environment, 2023)

Enhanced degradation of tetracycline under natural sunlight through the synergistic effect of Ag3PO4/MIL-101(Fe) photocatalysis and Fenton catalysis: Mechanism, pathway, and toxicity assessment - Xiaojuan Chen; Liang Yao; Juhua He; Jiesen Li; Song Xu; Ning Li; Yanping Zhu; Xin Chen; Runliang Zhu (Journal of Hazardous Materials, 2023)

The effect of in vitro digestion on the chemical and antioxidant properties of Lycium barbarum polysaccharides - Wenjun Zeng; Lulu Chen; Yanping Li; Jianlong Ma; Rui Yang; Jianbao Ding; Jin Yang (Food Hydrocolloids, 2023)

Oocyte Arrested at Metaphase II Stage were Derived from Human Pluripotent Stem Cells in vitro - Xiaoli Yu; Ning Wang; Xiang Wang; Hehe Ren; Yanping Zhang; Yingxin Zhang; Yikai Qiu; Hongyan Wang; Guoping Wang; Xiuying Pei; Ping Chen; Yahui Ren; et al. (Stem Cell Reviews and Reports, 2023)
Initiation of meiosis is the most difficult aspect of inducing competent oocytes differentiation from human stem cells in vitro . Human induced pluripotent stem cells (hiPSCs) and embryonic stem cells (hESCs) were cultured with follicle fluid, cytokines and small molecule to induced oocyte-like cells (OLCs) formation through a three-step induction procedure. Expression of surface markers and differentiation potential of germ cells were analyzed in vitro by flow cytometry, gene expression, immunocytochemistry, western blotting and RNA Sequencing. To induce the differentiation of hiPSCs into OLCs, cells were firstly cultured with a primordial germ cell medium for 10 days. The cells exhibited similar morphological features to primordial germ cells (PGCs), high expressing of germ cell markers and primordial follicle development associated genes. The induced PGCs were then cultured with the primordial follicle-like cell medium for 5 days to form the induced follicle-like structures (iFLs), which retained both primordial oocytes-like cells and granulosa-like cells. In the third step, the detached iFLs were harvested and transferred to the OLC-medium for additional 10 days. The cultured cells developed cumulus-oocyte-complexes (COCs) structures and OLCs with different sizes (50–150 μm diameter) and a zona pellucida. The in vitro matured OLCs had polar bodies and were arrested at metaphase II (MII) stage. Some OLCs were self-activated and spontaneously developed into multiple-cell structures similar to preimplantation embryos, indicating that OLCs were parthenogenetically activated though in vitro fertilization potential of OLCs are yet to be proved. in vitro maturation of OLCs derived from hiPSCs provides a new means to study human germ cell formation and oogenesis. Graphical Abstract

Effects of grazing exclusion on vegetation community characteristics over 22 years in the Zoige alpine meadows from China - Xue Jiang; Li He; Yanping Qu; Banghong Jian; Dongzhou Deng; Mei Liu; Jingtian Yang; Yunlong Ma; Dechao Chen; Yi Huang (Acta Oecologica, 2023)

Range restriction, climate variability and human‐related risks imperil lizards world‐wide - Chuanwu Chen; Marcel Holyoak; Junfeng Xu; Gabriel Henrique de Oliveira Caetano; Yanping Wang (Global Ecology and Biogeography, 2023)
Aims Identifying major reasons for species imperilment is a necessary step for conservation, but the degree to which we can generalize is hard for species‐rich yet less‐studied taxa, such as lizards. Here, we aim to bridge the gap by providing comprehensive analyses of the correlates and processes of species extinction and threats for global lizards. Location Global. Time period Current. Major taxa studied Lizards. Methods We compiled a dataset comprising extinction risk status, six intrinsic traits and seven extrinsic factors for 5256 lizard species. We carried out binomial distribution tests for 43 families and seven realms to check the non‐randomness in species extinction risk and used phylogenetic linear regressions to identify the key factors that relate to the extinction proneness of lizards and species subgroups. Based on the International Union for Conservation of Nature (IUCN) threat assessment, we identified major threats for global lizards and for major families and regions. Results We found strong evidence of taxonomic and geographical non‐randomness in the extinction risk of lizards. Geographical range size, human footprint and density, insular endemism, temperature and precipitation seasonality, and body size were key predictors of extinction risk, and the first three factors were also important across families and realms. Moreover, newly described species were more likely to have a restricted range size and a higher extinction risk. Globally, the most detrimental threat was habitat destruction, while overexploitation, species invasion and climate change varied widely in importance among species groups. Main conclusions Overall, we highlight the detrimental influences of range restriction, climate variability and anthropogenic threats to species persistence. We suggest that lizards are potentially at high risk of extinction owing to widespread human disturbance and that species with extinction‐prone traits require conservation prioritization. Moreover, lizards of different families and regions require different management strategies because of variation in extinction‐risk correlates and threats.

Analysis and realization of the influence of sea ice flexural strength on ice resistance in numerical simulation of icebreaking by icebreaker - Zhe Chen; Yanping He; Yupei Ren; Yadong Liu (Ocean Engineering, 2023)

Exploration of the metabolic flexibility of glycogen accumulating organisms through metatranscriptome analysis and metabolic characterization - Bin Zhao; Yanping Yang; Chen Zhao; Chunchun Zhang; Zhaohui Zhang; Liang Wang; Shang Wang; Jingfeng Wang (Journal of Environmental Sciences, 2023)

Ag3PO4-anchored La2Ti2O7 nanorod as a Z-Scheme heterostructure composite with boosted photogenerated carrier separation and enhanced photocatalytic performance under natural sunlight - Xiaojuan Chen; Jieming Chen; Ning Li; Jiesen Li; Juhua He; Song Xu; Yanping Zhu; Liang Yao; Yiqi Lai; Runliang Zhu (Environmental Pollution, 2023)

A general way to manipulate electrical conductivity of graphene - Liqing Chen; Nian Li; Xinling Yu; Shudong Zhang; Cui Liu; Yanping Song; Zhao Li; Shuai Han; Wenbo Wang; Pengzhan Yang; Na Hong; Sarmad Ali; et al. (Chemical Engineering Journal, 2023)

Computer-aided engineering of CRISPR-Cas proteins for enhanced human genome editing - Yangcan Chen; Yanping Hu; Shengqiu Luo; Xinge Wang; Bangwei Mao; Yi Chen; Jing Xu; Zhikun Li; Qi Zhou; Wei Li (Science China Life Sciences, 2023)

Osteopontin promotes microglia activation and aggravates neuromyelitis optica via interferon-gamma/nuclear factor kappa B/interleukin-12 signaling - Fengyi Chen; Yanping Wang (Molecular & Cellular Toxicology, 2023)

An improved zigzag-type printed circuit heat exchanger for supercritical CO2 Brayton cycles - Shenghui Liu; Cheng Gao; Minyun Liu; Yunxuan Chen; Jia Tang; Yanping Huang; Xiaoliang Zhu; Tianyang Xing (Annals of Nuclear Energy, 2023)

Ca2+-dependent TaCCD1 cooperates with TaSAUR215 to enhance plasma membrane H+-ATPase activity and alkali stress tolerance by inhibiting PP2C-mediated dephosphorylation of TaHA2 in wheat - Minghan Cui; Yanping Li; Jianhang Li; Fengxiang Yin; Xiangyu Chen; Lumin Qin; Lin Wei; Guangmin Xia; Shuwei Liu (Molecular Plant, 2023)

Characteristics of volatile organic compounds and secondary organic aerosol pollution in different functional areas of petrochemical industrial cities in Northwest China - Yanping Yang; Wenkai Guo; Jian Sun; Qiang Chen; Xianhong Meng; Lina Wang; Huijie Tao; Lili Yang (Science of The Total Environment, 2023)

Removal of chlorine, microparticles and water from high-viscosity liquids by a sand filter coupling hydrocyclone - Aosong Wei; Jianping Li; Minjie Shan; Wenjie Lv; Jianqi Chen; Pengbo Fu; Yanping Liu; Weichun Xu; Li Dai; Hualin Wang (Process Safety and Environmental Protection, 2023)

Numerical analysis of continuous icebreaking performance of icebreakers with different bow types - Yupei Ren; Zhe Chen; Yanping He; Chao Chen; Yadong Liu; Guangyao Zheng (Ocean Engineering, 2023)

Doing more with less: How to design a good subgroup governance model for the air pollution transport network in “2+26” cities of China? - Wenxia Zeng; Xi Chen; Huizhong Dong; Yanping Liu (Journal of Environmental Management, 2023)

Effects of solid-state fermentation with Bacillus subtilis Y4 on the quality of Yibin Yacai - Yuke Zou; Yixin Zhong; Qian Zhou; Zhenchao Jia; Qian Chen; Wei Xu; Yanping Wu; Shugu Wei; Kai Zhong; Hong Gao (Food Bioscience, 2023)

Preparation of recyclable and deformable POM microfiber for oil–water separation with nature-inspired top–bottom strategy - Wenbin Jin; Jingjing Wang; Hai Wan; Yuan Liang; Shuohan Huang; Yuwei Chen; Peng Wei; Qun Shao; Yanping Wang; Yong He; Yumin Xia (Chemical Engineering Journal, 2023)

Genetic characteristics and growth patterns of the hybrid grouper derived from the hybridization of Epinephelus fuscoguttatus (female) × Epinephelus polyphekadion (male) - Liu Cao; Pan Chen; Xingrong Hou; Jun Ma; Ning Yang; Yanping Xu; Yanjin Zhang; Anqi Zhao; Jiyuan Zhang; Xinyu Li; Hai Huang (Journal of Fish Biology, 2023)
Hybridization is one of the primary methods used to cultivate farmed grouper species. The hybrid grouper derived from crossing Epinephelus fuscoguttatus (♀) and E. polyphekadion (♂) exhibits growth superiority over its parents. The genetic characteristics and growth patterns of the hybrid grouper have not yet been defined. This study confirms the ploidy level of the hybrid grouper (2 n = 48) using chromosome count analysis and flow cytometry. The 5S rDNA family was used to evaluate genetic diversity. Only one 5S class (~400 bp) was detected in the hybrid grouper, which could be used to distinguish between two different types based on nucleotide sequences, likely representing homologous unit classes from the female and male parental species. Growth patterns of 5–8‐month‐old hybrid groupers were also monitored. In this phase, a positive allometric growth pattern in body mass with total length was found. Body height and body mass were significantly correlated based on correlation and path coefficient, suggesting that body height could serve as an excellent index to increase body mass. These results aid our understanding of the genetic evolution of the hybrid grouper and inform the development of improved rearing techniques.

MnOx@N-doped carbon nanosheets derived from Mn-MOFs and g-C3N4 for peroxymonosulfate activation: Electron-rich Mn center induced by N doping - Yue Zhao; Xiaohui Zhan; Yanping Sun; He Wang; Lei Chen; Junyan Liu; Huixiang Shi (Chemosphere, 2023)

Eukaryotic community succession on discarded face masks in the marine environment - Jie Ma; Fengyuan Chen; Zhen Zhang; Yanping Li; Jingli Liu; Ciara Chun Chen; Ke Pan (Science of The Total Environment, 2023)

Large-flake graphene-modified biochar for the removal of bisphenol S from water: rapid oxygen escape mechanism for synthesis and improved adsorption performance - Yurong Gao; Zheng Fang; Wenhui Lin; Hanbo Chen; Amit Bhatnagar; Jianhong Li; Yanhai Xie; Yanping Bao; Junfeng Chen; Hongting Zhao; Jun Meng; Wenfu Chen; et al. (Environmental Pollution, 2023)

Sinusoidal stretchable fibrous electrodes regulate cardiac contraction - Yanping Zhang; Alice Le Friec; Di Sun; Menglin Chen (Chemical Engineering Journal, 2023)

In situ transformation of bismuth-containing precursors into ultrathin bismuth nanosheets for enhanced electrochemical CO2 reduction - Aihao Xu; Dong Wei; Xiangyu Chen; Taishun Yang; Yanping Huang; Huibing He; Jing Xu (Chemical Engineering Journal, 2023)

Untargeted Metabolomic Analysis Reveals the Metabolic Disturbances and Exacerbation of Oxidative Stress in the Cerebral Cortex of a BTBR Mouse Model of Autism - Can Cao; Qi Li; Yanping Chen; Mingyang Zou; Caihong Sun; Xiangning Li; Lijie Wu (Journal of Molecular Neuroscience, 2023)

Growth, Muscle Nutrition Composition, and Digestive Enzyme Activities of the Juvenile and Adult Siniperca chuatsi Fed on Live Baits and a Formulated Diet - Liyun Ding; Yanping Zhang; Jiacheng Chen; Wenjing Chen; Shouqi Xie; Qingtang Chen (Fishes, 2022)
The present study aimed to evaluate the feasibility of a formulated diet to replace live baits as feed for Siniperca chuatsi. A 2 × 2 factorial design with three replicates was used to investigate the effects of conventional live baits (LB) and a formulated diet (FD) on the growth, muscle nutrition composition, and digestive enzyme activities of S. chuatsi at two growth stages. The results showed that the feed conversion ratio (FCR) in the FD group was significantly lower than that in the LB group. The final body weight (FBW) and weight gain (WG) were not significantly different between the two feeding modes. However, at the juvenile stage, the specific growth rate (SGR) in the FD group was significantly lower than that in the LB group. Muscle moisture, crude protein, and crude lipid contents were not influenced by dietary treatments. There were no significant differences in ∑EAA, ∑NEAA, and ∑AA compositions of the juvenile and adult stages fed the two kinds of diets. At the juvenile stage, histidine (His) content in the FD group was significantly higher than that in the LB group; at the adult stage, cysteine (Cys) content in the FD group was significantly higher than that in the LB group; at both growth stages, Met content in the FD group was significantly lower than that in the LB group. The FD group showed higher levels of ∑SFA, ∑HUFA, ∑n-3PUFA, n-3/n-6, EPA, and DHA than the LB group did, whilst the opposite occurred in the MUFA levels. In addition, fish fed with LB had significantly higher values of pepsin and intestinal trypsin activities in the juvenile fish compared to the FD group, but the activities were not significantly different between the two feeding modes at the adult stage. The activities of stomach and intestine amylase in the FD group were significantly higher than those in the LB group. Overall, these results showed that under long-term feeding conditions, S. chuatsi fed with the artificial diet had no significant difference in muscle crude protein, crude lipid, amino acid composition, and digestive capacity, but showed superiority in the composition of fatty acids such as EPA and DHA levels compared to the live baits group. Therefore, the artificially formulated diet might be a more appropriate feeding approach for sustainable development of the S. chuatsi industry.

Adsorption of di (2-ethylhexyl) phthalate (DEHP) to microplastics in seawater: a comparison between pristine and aged particles - Ke Pan; Ciara Chun Chen; Lin Lin; Huo Xu; Fengyuan Chen; Yanping Li; Xiaoshan Zhu; Jie Ma; Wenlu Lan (Bulletin of Environmental Contamination and Toxicology, 2022)

Geographic range size, water temperature, and extrinsic threats predict the extinction risk in global cetaceans - Chuanwu Chen; Thomas A. Jefferson; Bingyao Chen; Yanping Wang (Global Change Biology, 2022)
Despite the fact that cetaceans provide significant ecological contributions to the health and stability of aquatic ecosystems, many are highly endangered with nearly one‐third of species assessed as threatened with extinction. Nevertheless, to date, few studies have explicitly examined the patterns and processes of extinction risk and threats for this taxon, and even less between the two subclades (Mysticeti and Odontoceti). To fill this gap, we compiled a dataset of six intrinsic traits (active region, geographic range size, body weight, diving depth, school size, and reproductive cycle), six environmental factors relating to sea surface temperature and chlorophyll concentration, and two human‐related threat indices that are commonly recognized for cetaceans. We then employed phylogenetic generalized least squares models and model selection to identify the key predictors of extinction risk in all cetaceans, as well as in the two subclades. We found that geographic range size, sea surface temperature, and human threat index were the most important predictors of extinction risk in all cetaceans and in odontocetes. Interestingly, maximum body weight was positively associated with the extinction risk in mysticetes, but negatively related to that for odontocetes. By linking seven major threat types to extinction risk, we further revealed that fisheries bycatch was the most common threat, yet the impacts of certain threats could be overestimated when considering all species rather than just threatened ones. Overall, we suggest that conservation efforts should focus on small‐ranged cetaceans and species living in warmer waters or under strong anthropogenic pressures. Moreover, further studies should consider the threatened status of species when superimposing risk maps and quantifying risk severity. Finally, we emphasize that mysticetes and odontocetes should be conserved with different strategies, because their extinction risk patterns and major threat types are considerably different. For instance, large‐bodied mysticetes and small‐ranged odontocetes require special conservation priority.

The impact of international technical cooperation in new energy industry on carbon emissions: evidence from the top 30 countries in the global innovation index - Huajie Xu; Yanping Zhou; Huiying Chen; Jing Li; Yuanyuan Kou (Environmental Science and Pollution Research, 2022)

A novel antisense long non‐coding RNA participates in asexual and sexual reproduction by regulating the expression of GzmetE in Fusarium graminearum - Jie Wang; Wenping Zeng; Jiatao Xie; Yanping Fu; Daohong Jiang; Yang Lin; Weidong Chen; Jiasen Cheng (Environmental Microbiology, 2022)

Automatic identification of harmful algae based on multiple convolutional neural networks and transfer learning - Mengyu Yang; Wensi Wang; Qiang Gao; Chen Zhao; Caole Li; Xiangfei Yang; Jiaxi Li; Xiaoguang Li; Jianglong Cui; Liting Zhang; Yanping Ji; Shuqin Geng (Environmental Science and Pollution Research, 2022)

Degradation of sulfadiazine by UV/Oxone: roles of reactive oxidative species and the formation of disinfection byproducts - Juxiang Chen; Caiqiong Dai; Yanping Zhu; Yuqiong Gao; Wenhai Chu; Naiyun Gao; Qiongfang Wang (Environmental Science and Pollution Research, 2022)

Sequencing and comparative analysis of chloroplast genomes of three medicinal plants: Gentiana manshurica, G. scabra and G. triflora - Rong Zhao; Shuyue Yin; Jianing Xue; Chang Liu; Yanping Xing; Haibo Yin; Xue Ren; Jixiang Chen; Dingding Jia (Physiology and Molecular Biology of Plants, 2022)

HrreNet: semantic segmentation network for moderate and high-resolution satellite images - Yanping Li; Lu Wang; Lei Zhang; Haiwen Chen; Shiying Wang; Xiaoying Wang (International Journal of Remote Sensing, 2022)

Early-Holocene Paleo-Tropical Cyclone Activity Inferred from a Sedimentary Sequence in South Yellow Sea, East Asia - Geng Liu; Xibin Han; Yanping Chen; Jun Li; Lehui Song; Xin Zhou; Bangqi Hu; Liang Yi (Journal of Earth Science, 2022)

Detection of a major QTL and development of KASP markers for seed weight by combining QTL-seq, QTL-mapping and RNA-seq in peanut - Zhihui Wang; Liying Yan; Yuning Chen; Xin Wang; Dongxin Huai; Yanping Kang; Huifang Jiang; Kede Liu; Yong Lei; Boshou Liao (Theoretical and Applied Genetics, 2022)

X-ray Irradiation Improves Neurological Function Recovery of Injured Spinal Cord by Inhibiting Inflammation and Glial Scar Formation - Yi Wang; Yanping Niu; Fanguo Lin; Peng Su; Liesong Chen; Dong Liu; Yongming Sun (Journal of Molecular Neuroscience, 2022)

Indoor air pollution from solid fuel on children pneumonia in low- and middle-income countries: a systematic review and meta-analysis - Tianming Chen; Chao Zou; Yang Yuan; Jingjing Pan; Baoping Zhang; Liang Qiao; Yanping Li; Jia-yan Qian; Qingyuan Guo; Ye Yuan; Cheng Ding (Environmental Science and Pollution Research, 2022)

Correction to: Spindle‑related brain activation in patients with insomnia disorder: An EEG‑fMRI study - Yan Shao; Guangyuan Zou; Serik Tabarak; Jie Chen; Xuejiao Gao; Ping Yao; Jiayi Liu; Yuezhen Li; Nana Xiong; Wen Pan; Mengying Ma; Shuqin Zhou; et al. (Brain Imaging and Behavior, 2022)

Spindle-related brain activation in patients with insomnia disorder: An EEG-fMRI study - Yan Shao; Guangyuan Zou; Serik Tabarak; Jie Chen; Xuejiao Gao; Ping Yao; Jiayi Liu; Yuezhen Li; Nana Xiong; Wen Pan; Mengying Ma; Shuqin Zhou; et al. (Brain Imaging and Behavior, 2022)

Punch in the gut: parasite tolerance of phytochemicals reflects host diet - Evan C. Palmer‐Young; Ryan S. Schwarz; Yanping Chen; Jay D. Evans (Environmental Microbiology, 2022)
Summary Gut parasites of plant‐eating insects are exposed to antimicrobial phytochemicals that can reduce infection. Trypanosomatid gut parasites infect insects of diverse nutritional ecologies as well as mammals and plants, raising the question of how host diet‐associated phytochemicals shape parasite evolution and host specificity. To test the hypothesis that phytochemical tolerance of trypanosomatids reflects the chemical ecology of their hosts, we compared related parasites from honey bees and mosquitoes – hosts that differ in phytochemical consumption – and contrasted our results with previous studies on phylogenetically related, human‐parasitic Leishmania . We identified one bacterial and 10 plant‐derived substances with known antileishmanial activity that also inhibited honey bee parasites associated with colony collapse. Bee parasites exhibited greater tolerance of chrysin – a flavonoid found in nectar, pollen and plant resin‐derived propolis. In contrast, mosquito parasites were more tolerant of cinnamic acid – a product of lignin decomposition present in woody debris‐rich larval habitats. Parasites from both hosts tolerated many compounds that inhibit Leishmania , hinting at possible trade‐offs between phytochemical tolerance and mammalian infection. Our results implicate the phytochemistry of host diets as a potential driver of insect–trypanosomatid associations and identify compounds that could be incorporated into colony diets or floral landscapes to ameliorate infection in bees.

Microplastic Contamination on the Beaches of South China - Bingwen Chai; Yanping Li; Li Wang; Xiao-Tan Zhang; Yi-Ping Wan; Fengyuan Chen; Jie Ma; Wenlu Lan; Ke Pan (Frontiers in Marine Science, 2022)
Microplastics (MPs) have emerged as a pollutant of significant global concern. The sandy beach is a fragile environment that deserves our special attention with regard to MP contamination, as this area is a hotspot that accumulates large quantities of plastic waste. Notably, our current understanding of the MP distribution on beaches and the scale of contamination is far from sufficient. Hence, this study investigated the occurrence and characteristics of MPs on 14 beaches along the coast of South China. The MPs were ubiquitously distributed in the sand, most were small, less than 1 mm. A total of 18 types of polymers were identified in the sand, suggesting that diverse types of MPs are present on the beaches. Polyethylene, polypropylene, and polystyrene were the dominant types of MPs in most of our sampling sites. The MP abundance was higher in the upper layers (0–20 cm) of the beach than in the deeper layers (20–40 cm) of the sampling site when characterized by depth (Yangjiang beach). Our study demonstrates the extent and severity of MP pollution on the beaches of South China and provides implications for future remediation measures. More effort is needed to clarify the vertical distribution of MPs on beaches, especially for those MPs less than 1 μm.

Thiamine induces resistance in tobacco against black shank - Tian Suohui; Chen Yanping; Zi Shuhui; Li Zhihua; Jin Honggang; Liu Jun; Liu Tao (Australasian Plant Pathology, 2022)

Localization and regulatory function of Yin Yang 1 (YY1) in chicken testis - Ligen Chen; Lingyun Qiao; Yan Guo; Ying Huang; Wei Luo; Yanping Feng (Molecular Genetics and Genomics, 2022)

The expression and interaction proteins analysis of BjuFKF1/LKP2 in B. juncea - Jing Zeng; Anran Wu; Yuemin Yang; Liang Zhao; Li Chen; Chuanqi Wang; Xin Yang; Yanping Chen; Shiyan Liu; Pei Luo; Junli Wang (Molecular Genetics and Genomics, 2022)

A novel alphahypovirus that infects the fungal plant pathogen Sclerotinia sclerotiorum - Weibo Liang; Zhongbo Lu; Jie Duan; Daohong Jiang; Jiatao Xie; Jiasen Cheng; Yanping Fu; Tao Chen; Bo Li; Xiao Yu; Weidong Chen; Yang Lin (Archives of Virology, 2022)

Assessing risk to human health for heavy metal contamination from public point utility through ground dust: a case study in Nantong, China - Yanping Wang; Peng Qian; Dongming Li; Haifeng Chen; Xiangqian Zhou (Environmental Science and Pollution Research, 2021)

Magnetic minerals in Mid-Pleistocene sediments on the Caiwei Guyot, Northwest Pacific and their response to the Mid-Brunhes climate event - Liang Yi; Haifeng Wang; Geng Liu; Yanping Chen; Huiqiang Yao; Xiguang Deng (Acta Oceanologica Sinica, 2021)

A novel antisense long non‐coding RNA participates in asexual and sexual reproduction by regulating the expression of GzmetE in Fusarium graminearum - Jie Wang; Wenping Zeng; Jiatao Xie; Yanping Fu; Daohong Jiang; Yang Lin; Weidong Chen; Jiasen Cheng (Environmental Microbiology, 2021)
Summary Fusarium graminearum is an important worldwide pathogen that causes Fusarium head blight in wheat, barley, maize and other grains. LncRNAs play important roles in many biological processes, but little is known about their functions and mechanisms in filamentous fungi. Here, we report that a natural antisense RNA, GzmetE‐AS , is transcribed from the opposite strand of GzmetE . GzmetE encodes a homoserine O ‐acetyltransferase, which is important for sexual development and plant infection. The expression of GzmetE‐AS was increased significantly during the conidiation stage, while GzmetE was upregulated in the late stage of sexual reproduction. Overexpression of GzmetE‐AS inhibited the transcription of GzmetE . In contrast, the expression of GzmetE was significantly increased in GzmetE‐AS transcription termination strain GzmetE‐AS ‐T. Furthermore, GzmetE‐AS ‐T produced more perithecia and facilitated the ascospore discharge, resembling the phenotype of GzmetE overexpressing strains. However, overexpression of GzmetE‐AS in ∆dcl1/2 strain cannot inhibit the expression of GzmetE , and the GzmetE nat‐siRNA is also significantly reduced in ∆dcl1/2 mutant. Taken together, we have identified a novel antisense lncRNA GzmetE‐AS , which is involved in asexual and sexual reproduction by regulating its antisense gene GzmetE through RNAi pathway. Our findings reveal that the lncRNA plays critical roles in the development of F . graminearum .

Area threshold and trait–environment associations of butterfly assemblages in the Zhoushan Archipelago, China - Chuanwu Chen; Aichun Xu; Yanping Wang (Journal of Biogeography, 2021)
Aim An area threshold is usually considered as the point of abrupt change in the species–area relationship (SAR). Despite their widespread existence, few studies have considered the influence of data transformations on their presence or the mechanisms that generate them. The aims of this study were thus to test for the existence of an area threshold in butterfly assemblages and to compare trait–environment associations between small and large islands split by the threshold. Location Zhoushan Archipelago, China. Taxon Butterflies. Methods We used the line‐transect method to survey butterflies on 42 islands from July to August 2014. We also collected data on three commonly used ecological traits of butterflies (wingspan, wing loading and body weight). We transformed the butterfly datasets into three types (log‐log, semi‐log and untransformed) and fitted each of them using a set of breakpoint regression models. We then split all islands into small and large islands based on the area threshold and analysed the trait–environment associations for each island group. Results Two‐slope breakpoint models performed best for log‐log and semi‐log transformed datasets. However, the former exhibited a steep‐shallow shape with an area threshold of 0.820 km 2 and the latter was in shallow‐steep shape with a threshold of 17.022 km 2 . By contrast, no threshold was detected when using the untransformed power model. Moreover, for small islands, small area and large isolation were positively correlated with species with large wing loading and body weight. For large islands, however, the perimeter to area ratio (PAR) was significantly and positively related to wing loading. Main conclusions We found that data transformations may influence the detection of area thresholds. Trait–environment analyses can further provide novel and mechanistic insights into processes generating area thresholds. We urge that the influence of data transformations and ecological traits of species should be explicitly considered in future studies.

Associations of Serum Selenium Levels in the First Trimester of Pregnancy with the Risk of Gestational Diabetes Mellitus and Preterm Birth: a Preliminary Cohort Study - Peng Ju Liu; Aimin Yao; Liangkun Ma; Xiao Yan Chen; Song Lin Yu; Yanping Liu; Yi Xuan Hou (Biological Trace Element Research, 2021)

Associations of TMPRSS6 Polymorphisms with Gestational Diabetes Mellitus in Chinese Han Pregnant Women: a Preliminary Cohort Study - Peng Ju Liu; Aimin Yao; Xiao Yan Chen; Yanping Liu; Liangkun Ma; Yi Xuan Hou (Biological Trace Element Research, 2021)

Can supplementary pollen feeding reduce varroa mite and virus levels and improve honey bee colony survival? - Gloria DeGrandi-Hoffman; Vanessa Corby-Harris; Yanping Chen; Henry Graham; Mona Chambers; Emily Watkins deJong; Nicholas Ziolkowski; Yun Kang; Stephanie Gage; Megan Deeter; Michael Simone-Finstrom; Lilia de Guzman (Experimental and Applied Acarology, 2020)
Varroa destructor is an ectoparasitic mite of immature and adult honey bees that can transmit several single-stranded RNA viruses to its host. Varroa reproduce in brood cells, and mite populations increase as colonies produce brood in spring and summer. Mite numbers also can sharply rise, particularly in the fall, by the migration of varroa into hives on foragers. Colonies with high levels of varroa and viruses often die over the winter. Feeding colonies pollen might keep virus levels low and improve survival because of the positive effects of pollen on immunity and colony growth. We compared varroa and virus levels and overwinter survival in colonies with (fed) and without (unfed) supplemental pollen. We also measured the frequency of capturing foragers with mites (FWM) at colony entrances to determine its relationship to varroa and virus levels. Colonies fed supplemental pollen were larger than unfed colonies and survived longer. Varroa populations and levels of Deformed wing virus (DWV) rose throughout the season, and were similar between fed and unfed colonies. The growth of varroa populations was correlated with FWM in fed and unfed colonies, and significantly affected DWV levels. Increasing frequencies of FWM and the effects on varroa populations might reduce the positive influence of supplemental pollen on immune function. However, pollen feeding can stimulate colony growth and this can improve colony survival.

Differential effects of three amendments on the immobilisation of cadmium and lead for Triticum aestivum grown on polluted soil - Shengze Zhang; Lingtong Quan; Yanping Zhu; Jin Yan; Xiaoman He; Jia Zhang; Xiaoming Xu; Zhubing Hu; Feng Hu; Yahua Chen; Zhenguo Shen; Yan Xia (Environmental Science and Pollution Research, 2020)

Pseudorabies virus encephalitis in humans: a case series study - Siyuan Fan; Hongxun Yuan; Lei Liu; Hongfang Li; Shengnan Wang; Weili Zhao; Yihan Wu; Pei Wang; Yafang Hu; Jun Han; Yanli Lyu; Wuchao Zhang; et al. (Journal of NeuroVirology, 2020)

Evaluation of convection-permitting WRF CONUS simulation on the relationship between soil moisture and heatwaves - Zhe Zhang; Yanping Li; Fei Chen; Michael Barlage; Zhenhua Li (Climate Dynamics, 2020)

Occurrence and impacts of tropical cyclones over the southern South China Sea - Yanping Shi; Yan Du; Zesheng Chen; Wen Zhou (International Journal of Climatology, 2020)
This study investigates the seasonal variation of tropical cyclone (TC) occurrences over the southern South China Sea (SCS) based on the Joint Typhoon Warning Center dataset during 1979–2016. In this region, TCs are most active from October to December (OND), rather than in the active TC season from July to October (JASO) in other western North Pacific (WNP). According to the location of their genesis, the southern SCS TCs are divided into two groups. One consists of TCs generating in the WNP, which are induced by a westward steering flow and move into the southern SCS in OND. The other group contains TCs generated locally in the SCS that move into the southern SCS, which peak in OND due to the positive relative vorticity and high genesis potential index (GPI). In this region, TC genesis is influenced by the El Niño‐Southern Oscillation (ENSO). On an interannual scale, TCs tend to occur in La Niña years due to high GPI. In addition, the mid‐level relative humidity and the low level vorticity play important roles in the contribution of the environmental factors of GPI during ENSO. Both composite analysis and a case study show the impact of TCs on precipitation. TC occurrence is accompanied by heavy rainfall, which is triple the amount of climatological rainfall in OND during 1979–2016, over 15 mm⋅day −1 . Nevertheless, the influence of locally generated TCs, rather than TCs generated in the WNP, contributes to more heavy rainfall in the southern SCS.

Characterizing the effects of hypoxia on the metabolic profiles of mesenchymal stromal cells derived from three tissue sources using chemical isotope labeling liquid chromatography-mass spectrometry - Qiaoling Pan; Dan Wang; Deying Chen; Yanni Sun; Xudong Feng; Xiaowei Shi; Yanping Xu; Xian Luo; Jiong Yu; Yang Li; Hongcui Cao; Liang Li (Cell and Tissue Research, 2020)

Blueberry VcLon1 protease increases iron use efficiency by alleviating chloroplast oxidative stress - Jingya Zhong; Jiajia Gu; Yanping Guo; Shibei You; Fanglei Liao; Wenrong Chen; Weidong Guo (Plant and Soil, 2019)

Using 4-km WRF CONUS simulations to assess impacts of the surface coupling strength on regional climate simulation - Liang Chen; Yanping Li; Fei Chen; Michael Barlage; Zhe Zhang; Zhenhua Li (Climate Dynamics, 2019)

A Hedychium coronarium short chain alcohol dehydrogenase is a player in allo-ocimene biosynthesis - Hua Chen; Yuechong Yue; Rangcai Yu; Yanping Fan (Plant Molecular Biology, 2019)

Impact of the quasi-biweekly oscillation on the super typhoon tracks in winter over the western North Pacific - Yanping Shi; Yan Du; Zesheng Chen; Chunzai Wang (Climate Dynamics, 2019)

Beraprost sodium mitigates renal interstitial fibrosis through repairing renal microvessels - Shulin Li; Yanping Wang; Lu Chen; Zhuojun Wang; Guodong Liu; Bangjie Zuo; Caixia Liu; Dong Sun (Journal of Molecular Medicine, 2019)

Features of Shear Strength Parameters Reflecting Damage to Rock Caused by Water Invasion-Loss Cycles - Xuxin Chen; Yanping Gong (Geotechnical and Geological Engineering, 2019)

Novel mutations in ZP1, ZP2, and ZP3 cause female infertility due to abnormal zona pellucida formation - Zhou Zhou; Caixia Ni; Ling Wu; Biaobang Chen; Yao Xu; Zhihua Zhang; Jian Mu; Bin Li; Zheng Yan; Jing Fu; Wenjing Wang; Lin Zhao; et al. (Human Genetics, 2019)

Identification and molecular characterization of Serratia marcescens phages vB_SmaA_2050H1 and vB_SmaM_2050HW - Changyu Tian; Jiangtao Zhao; Zheng Zhang; Xiao Chen; Xiao Wei; Huan Li; Weishi Lin; Yuehua Ke; Lingfei Hu; Aimin Jiang; Ruo Feng; Wenhui Yang; et al. (Archives of Virology, 2019)

Active Biomonitoring of Metals with Cultured Anodonta woodiana: A Case Study in the Taihu Lake, China - Xiubao Chen; Yanping Su; Hongbo Liu; Jian Yang (Bulletin of Environmental Contamination and Toxicology, 2019)

Dioxin-like polychlorinated biphenyls in marine fish from Shandong, China, and human dietary exposure - Yanping Cao; Dafeng Jiang; Fenghua Li; Jindong Chen; Wei Li; Yanni Jiao; Lu Li (Food Additives & Contaminants Part B-Surveillance, 2018)

Two alphapartitiviruses co-infecting a single isolate of the plant pathogenic fungus Rhizoctonia solani - Ruiling Lyu; Yi Zhang; Qing Tang; Yangyi Li; Jiasen Cheng; Yanping Fu; Tao Chen; Daohong Jiang; Jiatao Xie (Archives of Virology, 2018)

Enhanced a novel β-agarase production in recombinant Escherichia coli BL21 (DE3) through induction mode optimization and glycerol feeding strategy - Zhuhua Chan; Xinglin Chen; Yanping Hou; Boliang Gao; Chungui Zhao; Suping Yang; Runying Zeng (Acta Oceanologica Sinica, 2018)

Do seasonal species assemblages differ in their biogeography? Evidence from the spatial structure of bird communities on land‐bridge islands - Chuanwu Chen; Marcel Holyoak; Xingfeng Si; Yanping Wang; Ping Ding (Journal of Biogeography, 2018)
Aim We tested the effects of season and migratory status (residents‐versus‐seasonal migrants) on island biogeography of bird assemblages through partitioning beta diversity into richness and turnover components and community nestedness metrics. We predicted that total beta diversity, the richness component of beta diversity and community nestedness will be lower for bird assemblages in winter than in summer, and lowest of all for winter visitors. These predictions were derived from published ideas about resource availability, movement and habitat choice in birds in different seasons. Location Thousand Island Lake, China. Methods Bird species were sampled using line transects on 36 islands during five breeding and winter seasons (2009−2014). Birds were grouped into assemblages of winter residents, winter visitors and summer residents. Associations between beta diversity partitioning, island area, isolation and habitat richness were tested using partial Mantel correlations. We complemented these tests with measures of nestedness and null model approaches. Results Contrary to expectation, beta diversity, nestedness and difference of beta diversity or its components from null models were higher for winter residents than either summer resident or winter visitor assemblages. As predicted, winter visitors showed little association with habitat richness, and beta diversity was rarely different from null communities. Summer residents had the highest correlations of beta diversity components with habitat richness, but showed the lowest level of total beta diversity, a low richness component and were anti‐nested (less nested than random). Main conclusions Substantial differences were found in the biogeography of winter‐versus‐summer residents, and seasonal visitor (migratory)‐versus‐resident bird assemblages, which match expectations derived from bird biology and population ecology. Summer residents highlighted the role of habitat‐related niche differences, whereas winter residents showed area‐related selective extinction. By contrast, winter visitors appeared to be more randomly distributed.

Soil dissimilatory nitrate reduction processes in the Spartina alterniflora invasion chronosequences of a coastal wetland of southeastern China: Dynamics and environmental implications - Dengzhou Gao; Xiaofei Li; Xianbiao Lin; Dianming Wu; Baoshi Jin; Yanping Huang; Min Liu; Xing Chen (Plant and Soil, 2017)

Determination of Fatty Acid Composition and Phospholipid Molecular Species of Large Yellow Croaker ( Pseudosciaena crocea ) Roe from China - Peng Liang; Xinwei Cheng; Yanping Xu; Wenjian Cheng; Lijiao Chen (Journal of Aquatic Food Product Technology, 2017)

Mineral composition variation in the shells of freshwater mussel Anodonta woodiana at different growth stages - Xiubao Chen; Yanping Su; Hongbo Liu; Tao Jiang; Jian Yang (Invertebrate Reproduction & Development, 2017)

Root order-dependent seasonal dynamics in the carbon and nitrogen chemistry of poplar fine roots - Hongying Chen; Yufeng Dong; Tan Xu; Yanping Wang; Huatian Wang; Baoli Duan (New Forests, 2017)

Recent land cover changes and sensitivity of the model simulations to various land cover datasets for China - Liang Chen; Zhuguo Ma; Rezaul Mahmood; Tianbao Zhao; Zhenhua Li; Yanping Li (Meteorology and Atmospheric Physics, 2017)

Synthesis and biological evaluation of novel anti-hepatitis C virus (HCV) agents: 2-hydroxylphenethyl sulfanyl-oxopyrimidines - Daochun Wu; Yue Feng; Hua Wang; Junfeng Yang; Xian Chen; Yueping Wang; Christopher Cong Lai; Yufang Zhang; Cong Li; Xueshan Xia; Yanping He (Medicinal Chemistry Research, 2017)

Continental-scale convection-permitting modeling of the current and future climate of North America - Changhai Liu; Kyoko Ikeda; Roy Rasmussen; Mike Barlage; Andrew J. Newman; Andreas F. Prein; Fei Chen; Liang Chen; Martyn Clark; Aiguo Dai; Jimy Dudhia; Trude Eidhammer; et al. (Climate Dynamics, 2017)

Bmi1 Regulates the Proliferation of Cochlear Supporting Cells Via the Canonical Wnt Signaling Pathway - Xiaoling Lu; Shan Sun; Jieyu Qi; Wenyan Li; Liman Liu; Yanping Zhang; Yan Chen; Shasha Zhang; Lei Wang; Dengshun Miao; Renjie Chai; Huawei Li (Molecular Neurobiology, 2017)

Molecular variation and expansion of a rice black-streaked dwarf virus population based on analysis of segment 1 in Jining, China - Yu Zhou; Qingchang Meng; Yanping Chen; Jirong Wu; Zhuanfang Hao; Zhenhua Wang; Degui Zhang; Mingshun Li; Hongjun Yong; Shihuang Zhang; Xinhai Li; Jianfeng Weng (Archives of Virology, 2016)

Characterization of eleven microsatellite markers for the tea geometrid Ectropis obliqua (Lepidoptera: Geometridae) - Shengli Jing; Baoxiao Zheng; Li Qiao; Kun Zhang; Gaoyang Chen; Shunqin Guo; Xiaoyan Huang; Yanping Gao; Lili Zhang; Hongyu Yuan (Applied Entomology and Zoology, 2016)

Effects of Calcium and Magnesium Ions on Acute Copper Toxicity to Glochidia and Early Juveniles of the Chinese Pond Mussel Anodonta woodiana - Hongbo Liu; Xiubao Chen; Yanping Su; Ik Joon Kang; Xuchun Qiu; Yohei Shimasaki; Yuji Oshima; Jian Yang (Bulletin of Environmental Contamination and Toxicology, 2016)

Isolation of a new carboline alkaloid from Trigonostemon lii - Hongmei Yang; Yanping Luo; Hongmei Zhao; Jichun Wu; Yegao Chen (Natural Product Research, 2016)

Biological Modulation of Mouse RPE Cells in Response to Subthreshold Diode Micropulse Laser Treatment - Zhouyue Li; Yanping Song; Xiao Chen; Zhongshan Chen; Qin Ding (Cell Biochemistry and Biophysics, 2015)

Reproductive management through integration of PGD and MPS-based noninvasive prenatal screening/diagnosis for a family with GJB2-associated hearing impairment - WenPing Xiong; DaYong Wang; Yuan Gao; Ya Gao; HongYang Wang; Jing Guan; Lan Lan; JunHao Yan; Liang Zong; Yuan Yuan; Wei Dong; SeXin Huang; et al. (Science China Life Sciences, 2015)

Morphological development and growth of the freshwater mussel Anodonta woodiana from early juvenile to adult - Xiubao Chen; Hongbo Liu; Yanping Su; Jian Yang (Invertebrate Reproduction & Development, 2015)

Effects of active, passive, and combined smoking on cervical cancer mortality: a nationwide proportional mortality study in Chinese urban women - Jingmei Jiang; Haiyu Pang; Boqi Liu; Philip C. Nasca; Biao Zhang; Yanping Wu; Wei Han; Margaret Gates; Tao Lu; Xiaonong Zou; Fang Xue; Lei Hou; et al. (Cancer Causes & Control, 2015)

Molecular characterization and phylogenetic analysis of ZmMCUs in maize - Qingchang Meng; Yuanyuan Chen; Meijing Zhang; Yanping Chen; Jianhua Yuan; Seth C. Murray (Biologia, 2015)

Exploring the Wnt Pathway-Associated LncRNAs and Genes Involved in Pancreatic Carcinogenesis Driven by Tp53 Mutation - Qi Wang; He Jiang; Chen Ping; Ruizhe Shen; Tingting Liu; Juanjuan Li; Yuting Qian; Yanping Tang; Shidan Cheng; Weiyan Yao; Lifu Wang (Pharmaceutical Research, 2015)

Comparative Genome Analysis of Lactobacillus casei: Insights into Genomic Diversification for Niche Expansion - Shuijing Yu; Yanping Peng; Yong Zheng; Wanyi Chen (Indian Journal of Microbiology, 2015)

Inhibition of the Activation and Recruitment of Microglia-Like Cells Protects Against Neomycin-Induced Ototoxicity - Shan Sun; Huiqian Yu; Hui Yu; Mei Honglin; Wenli Ni; Yanping Zhang; Luo Guo; Yingzi He; Zhen Xue; Yusu Ni; Jin Li; Yi Feng; et al. (Molecular Neurobiology, 2015)

The association between C-159T polymorphism in CD14 gene and susceptibility to tuberculosis: a meta-analysis - Qing Yuan; Huifang Chen; Xueyan Zheng; Xiaming Chen; Qun Li; Yanping Zhang; Xiaorong Zhang; Tingli Shi; Junhua Zhou; Qing Chen; Shouyi Yu (Molecular Biology Reports, 2014)

Flying Insect Classification with Inexpensive Sensors - Yanping Chen; Adena Why; Gustavo Batista; Agenor Mafra-Neto; Eamonn Keogh (Journal of Insect Behavior, 2014)

Comparative Genomic Analysis of Two-Component Signal Transduction Systems in Probiotic Lactobacillus casei - Shuijing Yu; Yanping Peng; Wanyi Chen; Yangwu Deng; Yanhua Guo (Indian Journal of Microbiology, 2014)

The Role of ABA in the Maturation and Postharvest Life of a Nonclimacteric Sweet Cherry Fruit - Hao Luo; ShengJie Dai; Jie Ren; CaiXia Zhang; Ying Ding; Zhuang Li; Yufei Sun; Kai Ji; Yanping Wang; Qian Li; Pei Chen; Chaorui Duan; et al. (Journal of Plant Growth Regulation, 2014)

Contrasting patterns of river runoff and sea-ice melted water in the Canada Basin - Jinlu Tong; Min Chen; Yusheng Qiu; Yanping Li; Jianping Cao (Acta Oceanologica Sinica, 2014)

CRP Gene polymorphism contributes genetic susceptibility to dyslipidemia in Han Chinese population - Wenbin Wei; Song Yang; Yingru Qiu; Hairu Wang; Xianghai Zhao; Yanping Zhao; Yun Li; Ming Wu; Yanchun Chen; Wen Wang; Xiaoming Shi; Sijun Liu; et al. (Molecular Biology Reports, 2014)

Association study of common variations of FBN1 gene and essential hypertension in Han Chinese population - Jinfeng Chen; Song Yang; Xianghai Zhao; Jiahui Shen; Hairu Wang; Yanchun Chen; Yanni Ji; Wen Wang; Wei Zhou; Xuecai Wang; Junming Tang; Xiangfeng Lu; et al. (Molecular Biology Reports, 2014)

Transcriptome-wide analysis of dynamic variations in regulation modes of grapevine microRNAs on their target genes during grapevine development - Chen Wang; Xiangpeng Leng; Yanyi Zhang; Emrul Kayesh; Yanping Zhang; Xin Sun; Jinggui Fang (Plant Molecular Biology, 2014)

Study of the Mechanism of Bystander Effect of KDR-CDglyTK System Mediated by Adenovirus for the Treatment of Gastric Cancer - Li Qiang; Li Yanping; Huang Zonghai; Chen Fei; Li Zhou; Yu Jinlong (Cell Biochemistry and Biophysics, 2013)

Glycosylation analysis of recombinant neutral protease I from Aspergillus oryzae expressed in Pichia pastoris - Da Lei; Yang Xu; Qinghua He; Yifeng Pan; Bo Chen; Liang Xiong; Yanping Li (Biotechnology Letters, 2013)

Sciadopitysin: active component from Taxus chinensis for anti-Alzheimer's disease - Qiong Gu; Yanping Li; Yingchun Chen; Peifen Yao; Tianmiao Ou (Natural Product Research, 2013)

γ-Aminobutyric acid (GABA) homeostasis regulates pollen germination and polarized growth in Picea wilsonii - Yu Ling; Tong Chen; Yanping Jing; Lusheng Fan; Yinglang Wan; Jinxing Lin (Planta, 2013)

Alterations of Sodium and Potassium Channels of RGCs in RCS Rat with the Development of Retinal Degeneration - Zhongshan Chen; Yanping Song; Junping Yao; Chuanhuang Weng; Zheng Qin Yin (Journal of Molecular Neuroscience, 2013)

Transcriptional Regulation of Genes Encoding Key Enzymes of Abscisic Acid Metabolism During Melon (Cucumis melo L.) Fruit Development and Ripening - Yufei Sun; Pei Chen; Chaorui Duan; Pang Tao; Yanping Wang; Kai Ji; Yin Hu; Qian Li; Shengjie Dai; Yan Wu; Hao Luo; Liang Sun; et al. (Journal of Plant Growth Regulation, 2013)

Therapy with Astragalus polysaccharides rescues lipotoxic cardiomyopathy in MHC-PPARα mice - Wei Chen; Wenjie Chen; Yanping Xia; Xuelan Zhao; Hao Wang; Maohua Yu; Yiming Li; Hongying Ye; Yu Zhang (Molecular Biology Reports, 2013)

Soil Respiration and N2O Flux Response to UV-B Radiation and Straw Incorporation in a Soybean–Winter Wheat Rotation System - Zhenghua Hu; Hailing Cui; Shutao Chen; Shuanghe Shen; Hanmao Li; Yanping Yang; Cenzi Li (Water, Air, & Soil Pollution, 2013)

RETRACTED ARTICLE: Isolation and analysis of homoeologous genes encoding gibberellin 2-oxidase 3 isozymes in common wheat - QIUFANG CHEN; HUIYUAN YA; SHIMING LI; YANPING YANG; GUANGYONG QIN; XUELI AN; DAOWEN WANG; KUNPU ZHANG; ZHEN JIAO (Journal of Genetics, 2012)

The nuclear translocation of endostatin is mediated by its receptor nucleolin in endothelial cells - Nan Song; Yanping Ding; Wei Zhuo; Ting He; Zhiguang Fu; Yang Chen; Xiaomin Song; Yan Fu; Yongzhang Luo (Angiogenesis, 2012)

Reference gene selection for qPCR in Ammopiptanthus mongolicus under abiotic stresses and expression analysis of seven ROS-scavenging enzyme genes - Jing Shi; Meiqin Liu; Junna Shi; Guangshun Zheng; Yanping Wang; Jinyu Wang; Yuzhen Chen; Cunfu Lu; Weilun Yin (Plant Cell Reports, 2012)

Preliminary assessment of heavy metal contamination in surface water and sediments from Honghu Lake, East Central China - Ying Hu; Shihua Qi; Chenxi Wu; Yanping Ke; Jing Chen; Wei Chen; Xiangyi Gong (Frontiers of Earth Science, 2012)

Inactivation of the extracytoplasmic function sigma factor Sig6 stimulates avermectin production in Streptomyces avermitilis - Libin Jiang; Yanping Liu; Pan Wang; Ying Wen; Yuan Song; Zhi Chen; Jilun Li (Biotechnology Letters, 2011)

Study on gastric cancer blood plasma based on surface-enhanced Raman spectroscopy combined with multivariate analysis - ShangYuan Feng; JianJi Pan; YanAn Wu; Duo Lin; YanPing Chen; GangQin Xi; JuQiang Lin; Rong Chen (Science China Life Sciences, 2011)

Stratification of Archaeal communities in shallow sediments of the Pearl River Estuary, Southern China - Lijing Jiang; Yanping Zheng; Jinquan Chen; Xiang Xiao; Fengping Wang (Antonie van Leeuwenhoek, 2011)

Spatial and temporal variations of macro- and mesozooplankton community in the Huanghai Sea (Yellow Sea) and East China Sea in summer and winter - Hongju Chen; Yanping Qi; Guangxing Liu (Acta Oceanologica Sinica, 2011)

Single nucleotide polymorphism of FSHβ gene associated with reproductive traits in Japanese flounder (Paralichthys olivaceus) - Feng He; Haishen Wen; Dahui Yu; Jifang Li; Bao Shi; Caifang Chen; Jiaren Zhang; Guoxiong Jin; Xiaoyan Chen; Dan Shi; Yanping Yang (Journal of Ocean University of China, 2010)

Impacts of climatic factors on runoff coefficients in source regions of the Huanghe River - Liqun Chen; Changming Liu; Yanping Li; Guoqiang Wang (Chinese Geographical Science, 2007)

ABCC10, ABCC11, and ABCC12 - Gary D. Kruh; Yanping Guo; Elizabeth Hopper-Borge; Martin G. Belinsky; Zhe-Sheng Chen (Pflügers Archiv - European Journal of Physiology, 2007)

Baculovirus-based expression of an insect viral protein in 12 different insect cell lines - Yanping Chen; Dawn Gundersen-Rindal; Dwight Lynn (In Vitro Cellular & Developmental Biology - Animal, 2005)

Novel murine mammary epithelial cell lines that form osteolytic bone metastases: Effect of strain background on tumor homing - Yanping Chen; Susan R. Rittling (Clinical & Experimental Metastasis, 2003)